Electrode for power storage device, power storage device and secondary battery
By adopting a composite film structure between the current collector and the lead of the lithium-ion secondary battery and setting a recess on the lead, the problem of the current collector and the lead is not firmly connected, and the reliability of the power storage device is improved.
Patent Information
- Application Number
- CN202180004861.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-03-31
AI Technical Summary
In lithium-ion secondary batteries, improvements in electrical connections between current collectors and leads and mechanical connections can improve the reliability of the electrical storage device.
An electrode for an electric storage device including a conductor plate and a composite film is adopted. The composite film has a layer of insulating material, a first conductive layer and a second conductive layer. The first conductive layer is connected to the conductor plate, and the second conductive layer is connected to the first conductive layer at a specific position to form an electrical connection. The recesses are provided on the leads to connect to the composite film conductive layer to increase the interface area to improve the bonding strength.
By increasing the interface area between the lead and the composite film, the area of mechanical connection and electrical connection is improved, the bonding strength between the lead and the composite film is enhanced, thereby improving the reliability of electrical storage devices such as secondary batteries.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode for a power storage device, and a power storage device and a secondary battery having the electrode for a power storage device. Background Art
[0002] Regarding the current collector of a secondary battery, a technique using a composite material having metal layers formed on both sides of a resin film is disclosed. Patent Documents 1 and 2 listed below disclose lithium ion secondary batteries using such a composite material as a current collector.
[0003] [Prior art literature]
[0004] [Patent Document]
[0005] Patent Document 1: U.S. Patent Application Publication No. 2020 / 0373584
[0006] Patent Document 2: Japanese Patent Application Publication No. 2012-155974 Summary of the invention
[0007] [Technical problem to be solved by the invention]
[0008] In a power storage device such as a lithium ion secondary battery, a conductive member (lead) is generally connected to a current collector in order to extract power outside the outer casing. Improving the electrical and mechanical connection between the current collector and the lead can improve the reliability of the power storage device.
[0009] [Methods for solving technical problems]
[0010] An electrode for a storage device according to one embodiment of the present invention includes: a conductor plate having a first surface including at least one first recess, and a second surface located on the opposite side of the first surface, the first surface having a first region located outside the first recess; and a first composite film having a first layer containing an insulating material, a first conductive layer, and a second conductive layer, the first layer being located between the first conductive layer and the second conductive layer, the first conductive layer of the first composite film being connected to the conductor plate at the first recess, and the second conductive layer of the first composite film being connected to the first conductive layer at a position overlapping with the first recess when viewed from the normal direction of the first region of the conductor plate.
[0011] [Effects of the invention]
[0012] According to the embodiment of the present invention, the reliability of the power storage device can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a partial cross-sectional view showing an example of an electric storage device according to one embodiment of the present invention.
[0014] Figure 2 is from Figure 1 The electric storage device shown is an exploded perspective view in which the single cells and leads are removed.
[0015] Figure 3 About Figure 2 Schematic cross-sectional view of a portion of the first electrode shown.
[0016] Figure 4 About Figure 2 Schematic cross-sectional view of a portion of the second electrode shown.
[0017] Figure 5 Yes means Figure 2 A schematic perspective view of the third portion and its surroundings between the second electrode and the lead in the structure shown.
[0018] Figure 6 This is a schematic perspective view showing an enlarged portion of a laminate of a composite film bonded to a lead wire.
[0019] Figure 7 It is a schematic partial cross-sectional view for explaining the structure of the third portion between the composite film and the lead.
[0020] Figure 8 is Figure 7 Magnified view of the area indicated by the dotted circle in FIG.
[0021] Fig. 9 This is a schematic diagram showing a microscope image of a cross section of a recessed portion formed on the upper surface of a lead and its surroundings in a line graph.
[0022] Fig.10 This is a schematic diagram showing a microscope image of a cross section of a laminate of a composite film and a lead in a line graph.
[0023] Fig.11 This is a schematic partial cross-sectional view showing an example of the cross-sectional shape of a composite film connected to a lead wire.
[0024] Fig.12 This is a schematic partial cross-sectional view showing another example of the cross-sectional shape of the composite film connected to the lead wire.
[0025] Fig.13 This is a schematic partial cross-sectional view showing still another example of the cross-sectional shape of the composite film connected to the lead wire.
[0026] Fig.14 This is a schematic partial cross-sectional view showing still another example of the cross-sectional shape of the composite film connected to the lead wire.
[0027] Fig.15This is a schematic partial cross-sectional view showing, in enlarged form, a connection portion between a lowermost composite film in a composite film stack and a lead.
[0028] Fig.16 It is a schematic plan view showing an example of the shape and arrangement of the recessed portions formed on the upper surface of the lead.
[0029] Fig.17 It is a schematic plan view showing another example of the shape and arrangement of the recessed portion formed on the upper surface of the lead.
[0030] Fig.18 It is a schematic plan view showing another example of a plurality of recessed portions that can be formed in a laminated body of a composite film.
[0031] Fig.19 This is a schematic plan view showing still another example of a plurality of recessed portions that can be formed in a laminated body of a composite film.
[0032] Fig. 20 This is a plan view showing an enlarged view of one of a plurality of recessed portions that can be formed in a laminated body of a composite film.
[0033] Fig.21 It is a schematic plan view showing still another example of the shape and arrangement of the recessed portions formed on the upper surface of the lead.
[0034] Fig. 22 It means that it can be formed on the upper surface with Fig.21 FIG. 1 is a schematic plan view of an example of the shape of a plurality of recessed portions of a composite film in which lead wires of the recessed portions are connected.
[0035] Fig.23 Yes Fig. 22 A top view showing an enlarged representation of one of the plurality of recesses shown.
[0036] Fig.24 It is a schematic plan view showing still another example of the shape and arrangement of the recessed portions formed on the upper surface of the lead.
[0037] Fig.25 Yes means Fig.24 A schematic cross-sectional view of a portion of the structure shown.
[0038] Fig.26 It means that it can be formed on the upper surface with Fig.24 FIG. 1 is a schematic plan view of an example of the shape of a plurality of recessed portions of a composite film in which lead wires of the recessed portions are connected.
[0039] Fig. 27 It is a schematic plan view showing still another example of the shape and arrangement of the recessed portions formed on the upper surface of the lead.
[0040] Fig.28It means that it can be formed on the upper surface with Fig. 27 FIG. 1 is a schematic plan view of an example of the shape of a plurality of recessed portions of a composite film in which lead wires of the recessed portions are connected.
[0041] Fig.29 It is a schematic plan view showing still another example of the shape and arrangement of the recessed portions formed on the upper surface of the lead.
[0042] Fig.30 It means that it can be formed on the upper surface with Fig.29 FIG. 1 is a schematic plan view of an example of the shape of a plurality of recessed portions of a composite film in which lead wires of the recessed portions are connected.
[0043] Fig.31 It is a schematic plan view showing still another example of the shape and arrangement of the recessed portions formed on the upper surface of the lead.
[0044] Fig.32 It means that it can be formed on the upper surface with Fig.31 FIG. 1 is a schematic plan view of an example of the shape of a plurality of recessed portions of a composite film in which lead wires of the recessed portions are connected.
[0045] Fig.33 It is a schematic plan view showing still another example of the shape and arrangement of the recessed portions formed on the upper surface of the lead.
[0046] Fig.34 It means that it can be formed on the upper surface with Fig.33 FIG. 1 is a schematic plan view of an example of the shape of a plurality of recessed portions of a composite film in which lead wires of the recessed portions are connected.
[0047] Fig.35 It is a schematic plan view showing still another example of the shape and arrangement of the recessed portions formed on the upper surface of the lead.
[0048] Fig.36 It means that it can be formed on the upper surface with Fig.35 FIG. 1 is a schematic plan view of an example of the shape of a plurality of recessed portions of a composite film in which lead wires of the recessed portions are connected.
[0049] Fig.37 It is a schematic plan view showing still another example of the shape and arrangement of the recessed portions formed on the upper surface of the lead.
[0050] Fig.38 It means that it can be formed on the upper surface with Fig.37 FIG. 1 is a schematic plan view of an example of the shape of a plurality of recessed portions of a composite film in which lead wires of the recessed portions are connected.
[0051] Fig.39 This is a schematic cross-sectional view for explaining another example of the connection between the electrode and the lead in the power storage device according to one embodiment of the present invention.
[0052] Fig.40 This is a partial cross-sectional view showing a modification of the power storage device according to one embodiment of the present invention.
[0053] Fig.41 Yes Fig.40 The illustrated electric storage device is a schematic exploded perspective view showing a single cell removed from the device.
[0054] Fig.42 This is a partial cross-sectional view showing another modified example of the power storage device according to one embodiment of the present invention.
[0055] Fig.43 It is used to illustrate Fig.42 Schematic exploded view of the stacked structure of the first electrode, the second electrode, and the separator in the single cell shown.
[0056] Fig.44 is from Fig.42 The unit cell shown is a schematic perspective view showing the second electrode removed.
[0057] Fig.45 is from Fig.42 The unit cell shown is a schematic perspective view showing the first electrode removed.
[0058] Fig.46 This is a partial cross-sectional view showing still another modified example of the power storage device according to one embodiment of the present invention.
[0059] Fig.47 It is used to illustrate Fig.46 Schematic exploded view of the stacked structure of the first electrode, the second electrode, and the separator in the single cell shown.
[0060] Fig.48 This is a flowchart for explaining an exemplary method of manufacturing a power storage device according to another embodiment of the present invention.
[0061] Fig.49 This is a perspective view for explaining an exemplary tip shape of a horn that can be used for ultrasonic bonding between a lead wire and a composite film.
[0062] Fig.50 This is a perspective view showing another example of the tip shape of a horn that can be used for ultrasonic bonding between a lead wire and a composite film.
[0063] Fig.51 It is a schematic cross-sectional view for explaining an exemplary manufacturing process of the power storage device.
[0064] Fig.52 It is a schematic cross-sectional view for explaining an exemplary manufacturing process of the power storage device.
[0065] Fig.53 It is a schematic enlarged cross-sectional view for explaining an exemplary manufacturing process of the power storage device.
[0066] Fig.54 This is a schematic diagram showing an example of a microscope image of the lower surface of the lead after ultrasonic bonding is performed using a line graph.
[0067] Fig.55 This is a partial cross-sectional view showing an example of an electric storage device according to still another embodiment of the present invention.
[0068] Fig.56 yes Fig.55 A schematic partial cross-sectional view of the power storage device shown.
[0069] Fig.57 This is a schematic cross-sectional view for explaining the microscopic geometrical properties of a bonding head used in the production of battery 1-1.
[0070] Fig.58 This is a schematic diagram showing, as a line graph, a microscope image of the third portion on the positive electrode side of the battery 1 - 1 observed in the lamination direction of the composite films.
[0071] Fig.59 1 is a schematic diagram showing, as a line graph, a microscope image of a cross section of a joining portion on the positive electrode side of the battery 1 - 1 after ultrasonic bonding is performed.
[0072] Fig.60 is a schematic diagram showing a microscope image of the joint portion on the positive electrode side of battery 1-1 using a line graph. Fig.59 A magnified portion of the image.
[0073] Fig.61 This is a schematic diagram of a microscope showing a schematic cross-sectional view for explaining the geometrical properties of a bonding tip used in manufacturing the battery 2 by means of a line graph.
[0074] Fig.62 This is a schematic diagram showing, as a line graph, a microscope image of the third portion on the positive electrode side of the battery 2 observed in the lamination direction of the composite film.
[0075] Fig.63 It is a schematic cross-sectional view for explaining the geometrical properties of a welding head used in manufacturing the battery 3 .
[0076] Fig.64 This is a schematic diagram showing, as a line graph, a microscope image of a third portion on the positive electrode side of the battery 3 observed in the lamination direction of the composite film.
[0077] Fig.65 Yes means Figure 2A schematic perspective view of the third portion and its surroundings between the first electrode and the lead in the structure shown.
[0078] Fig.66 This is a schematic perspective view showing an enlarged portion of a laminate of a composite film bonded to a lead wire.
[0079] Fig.67 It is a schematic partial cross-sectional view for explaining the structure of the third portion between the composite film and the lead. DETAILED DESCRIPTION
[0080] Hereinafter, the embodiments of the present invention will be described with reference to the accompanying drawings. The numerical values, shapes, materials, steps, the order of the steps, etc. mentioned in the following description are only examples, and various changes can be made thereto as long as no technical contradiction occurs. In addition, the embodiments described below are also only examples, and various combinations can be made as long as no technical contradiction occurs.
[0081] For the sake of convenience, the sizes and shapes of the components shown in the drawings of the present invention are sometimes exaggerated. In addition, in order to avoid excessive complexity, in the drawings of the present invention, some components are sometimes taken out for illustration, or some elements are omitted for illustration. Therefore, the sizes of the components and the configuration of the components shown in the drawings of the present invention may not reflect the sizes of the components and the configuration of the components in the actual device.
[0082] In the following, the structure, shape, etc. of a component are sometimes described as, for example, a plane figure such as a polygon or a circle, or a three-dimensional figure such as a cuboid, a pyramid or a cone. However, the illustration of a figure in such an explanation does not mean that the structure, shape, etc. of a component are strictly mathematically consistent with such a figure. For example, an actual component may also have a shape in which the edge or face of the illustrated figure has been partially deformed. The "vertical" and "orthogonal" in the present invention are not limited to two straight lines, edges, faces, etc. that are strictly at an angle of 90°, but also include situations in the range of 90°±5°.
[0083] In this specification, the term "single cell" refers to a structure in which at least one pair of positive and negative electrodes are integrally assembled. The term "battery" in this specification is used as a term for various forms such as a battery module (battery module) and a battery pack (battery pack) having more than one "single cell" electrically connected to each other.
[0084] [Embodiment 1 of Power Storage Device]
[0085] Figure 1 An example of the structure of an electric storage device according to one embodiment of the present invention is shown. Here, a stacked lithium ion secondary battery is exemplified as the electric storage device.
[0086] Figure 1 The lithium ion secondary battery 100A shown has: a single cell 200A of one or more groups including a positive electrode and a negative electrode; a pair of conductive plates 250 and 260 connected to the single cell 200A; an outer casing 300 covering the single cell 200A; and an electrolyte 290. Here, as the secondary battery 100A, a so-called pouch type or laminated type lithium ion secondary battery is exemplified.
[0087] The single cell 200A is accommodated in a space formed inside the outer casing 300. The conductor plate 250 has a portion located inside the outer casing 300 and a portion located outside the outer casing 300. Similarly, the conductor plate 260 also has a portion located inside the outer casing 300 and a portion located outside the outer casing 300. The portion of the conductor plate 250 that is led out to the outside of the outer casing 300 functions as a positive terminal of the secondary battery 100A, and the portion of the conductor plate 260 that is led out to the outside of the outer casing 300 functions as a negative terminal of the secondary battery 100A. Hereinafter, the conductor plate 250 and the conductor plate 260 are referred to as "lead 250" and "lead 260", respectively.
[0088] The space inside the outer casing 300 further contains an electrolyte 290. The electrolyte 290 is, for example, a non-aqueous electrolyte. When the non-aqueous electrolyte is used for the electrolyte 290, a sealing material (for example, a resin film such as polypropylene, etc.) for preventing leakage of the electrolyte can be arranged between the outer casing 300 and the lead 250, and between the outer casing 300 and the lead 260. Figure 1 (not shown in the figure).
[0089] Figure 2 Yes Figure 1 The single cell and a pair of leads shown are removed and schematically represented. Figure 2 In the illustrated structure, the cell 200A includes: one or more first electrodes 210A, one or more second electrodes 220A, and one or more third layers 270A. The first electrode 210A is, for example, a positive electrode of the cell 200A, and the second electrode 220A is a negative electrode of the cell 200A. Figure 2 In the illustrated structure, the first electrode 210A, the second electrode 220A, and the third layer 270A are all in sheet form. Figure 2 In FIG. 1 , for convenience of explanation, arrows are shown indicating three directions orthogonal to each other, namely, the X direction, the Y direction, and the Z direction. Figure 2 In the example shown, the first electrode 210A, the second electrode 220A, and the third layer 270A are stacked along the Z direction in the figure.
[0090] like Figure 2As schematically shown, the single cell 200A has a structure in which the first electrode 210A and the second electrode 220A are alternately stacked with the third layer 270A therebetween. The third layer 270A contains an insulating material and functions as a separator of the single cell 200A. The single cell 200A contains, for example, 19 sheets of the first electrode 210A and 20 sheets of the second electrode 220A. In this case, the single cell 200A contains a total of 38 sheets of the third layer 270A respectively located between the first electrode 210A and the second electrode 220A. Here, the Z direction in the figure coincides with the direction in which the first electrode 210A, the second electrode 220A, and the third layer 270A are stacked. In this specification, the Z direction in the figure is sometimes referred to as the stacking direction.
[0091] Each first electrode 210A includes a composite film 215A having a first surface 215a and a second surface 215b and a first material layer 212. The first surface 215a is the upper surface of the composite film 215A, and the second surface 215b is the lower surface of the composite film 215A facing the side opposite to the first surface 215a in the Z direction in the figure. The first material layer 212 is provided on the first surface 215a and the second surface 215b of the composite film 215A. The first material layer 212 is a layer of the single cell 200A, for example, containing a positive electrode active material. In addition, in the description of the present invention, sometimes, terms including "upper surface", "lower surface", "upper layer" and "lower layer" are used. However, this is for the convenience of explaining the relative arrangement between components, and is not intended to limit the posture of the storage device when in use. For example, the "upper surface" refers to the surface located on the positive side of the Z direction in the figure, and the "lower surface" refers to the surface located on the negative side of the Z direction in the figure.
[0092] Each second electrode 220A includes: a composite film 225A having a third surface 225a and a fourth surface 225b, and a second material layer 222. The third surface 225a is the upper surface of the composite film 225A, and the fourth surface 225b is the lower surface of the composite film 225A facing the side opposite to the third surface 225a in the Z direction in the figure. The second material layer 222 is a layer of the single cell 200A, for example, containing a negative electrode active material. The second material layer 222 is provided on one or both of the third surface 225a and the fourth surface 225b of the composite film 225A. However, among the plurality of second electrodes 220A, a second electrode 220A located at the uppermost layer of the stacked structure of the first electrode 210A and the second electrode 220A may not have the second material layer 222 on its third surface 225a. Similarly, among the plurality of second electrodes 220A, one second electrode 220A located at the bottom layer of the stacked structure of the first electrode 210A and the second electrode 220A may not have the second material layer 222 on the fourth surface 225 b opposite to the third surface 225 a .
[0093] Each third layer 270A is disposed between the first electrode 210A and the second electrode 220A located closest to the first electrode 210A. The third layer 270A is formed of an insulating material such as resin to prevent direct contact between the first material layer 212 on the composite film 215A and the second material layer 222 on the composite film 225A.
[0094] As described later, the composite film 215A has a conductive layer in contact with the first material layer 212 and functions as a current collector of the first electrode 210A. Similarly, the composite film 225A has a conductive layer in contact with the second material layer 222 and functions as a current collector of the second electrode 220A. Figure 2 As schematically shown, the composite film 215A of each first electrode 210A has regions on the first surface 215a and the second surface 215b where the first material layer 212 is not disposed. Figure 2 In the figure, the regions are shown separated from each other, but in the actual device, these regions are physically in contact with each other and electrically connected between different composite films 215A. The same is true for the second electrode 220A, that is, the third surface 225a and the fourth surface 225b of each composite film 225A respectively include: regions where the second material layer 222 is not configured and the plurality of second electrodes 220A are connected to each other. Figure 2 This is an example of a structure in which a plurality of groups each including one first electrode 210A and one second electrode 220A are electrically connected in parallel.
[0095] exist Figure 2 In the example shown, the lead 250 is connected to the second surface 215b of one of the plurality of first electrodes 210A located at the bottom layer of the stacked structure of the first electrode 210A and the second electrode 220A. In addition, the lead 260 is connected to the fourth surface 225b of one of the plurality of second electrodes 220A located at the bottom layer of the stacked structure of the first electrode 210A and the second electrode 220A.
[0096] In the embodiment of the present invention, composite films 215A and 225A are composite materials in which conductive layers are arranged on both sides of a film containing an insulating material such as a resin. As described in detail later with reference to the accompanying drawings, in the embodiment of the present invention, an electrical connection is formed between the two conductive layers in the composite film, and an electrical connection is also formed between the conductive layer in the composite film and the lead. In this case, it is beneficial to provide one or more recesses on the surface of the lead on the side opposite to the composite film, and to use these recesses to achieve mechanical and electrical connection between the lead and the conductive layer in the composite film.
[0097] According to one embodiment of the present invention, since the lead is connected to the conductive layer of the composite film by using one or more recesses provided in the lead, the area of the interface between the lead and the composite film can be increased. Since the area where the mechanical connection and electrical connection are formed between the lead and the composite film can be expanded, they can be more firmly bonded to each other, and the bonding strength is improved. As a result, the reliability of power storage devices such as secondary batteries can be improved. The first electrode 210A, the second electrode 220A and the leads 250, 260, and the connection therebetween are described in more detail below.
[0098] Figure 3 Schematically Figure 2 A portion of the cross section of the first electrode is shown. Figure 2 Similarly, in Figure 3 , arrows indicating the X direction, Y direction, and Z direction orthogonal to each other are shown. In other drawings of the present invention, arrows indicating the X direction, Y direction, and Z direction are sometimes also shown.
[0099] As reference Figure 2 As described above, the first electrode 210A includes the composite film 215A and the first material layer 212 supported by the composite film 215A. The first material layer 212 is disposed on both sides of the first surface 215a side and the second surface 215b side of the composite film 215A.
[0100] like Figure 3 As shown in the figure, the first surface 215a and the second surface 215b of the composite film 215A respectively have an area overlapping with the first material layer 212 in the Z direction and an area located outside the first material layer 212. For the sake of convenience, in the following description, the area of the composite film 215A that does not overlap with the first material layer 212 in the Z direction in the figure, that is, located outside the first material layer 212 is sometimes referred to as the "lead area 210t".
[0101] exist Figure 3 In the illustrated structure, the composite film 215A includes: a first conductive layer 11, a second conductive layer 12, and a first layer sandwiched between the first conductive layer 11 and the second conductive layer 12. The first conductive layer 11 has: an upper surface 11a located on the first layer 14 side of the surface of the first conductive layer 11; and a lower surface 11b located on the opposite side of the upper surface 11a. The second conductive layer 12 has: a lower surface 12b located on the first layer 14 side of the surface of the second conductive layer 12; and an upper surface 12a located on the opposite side of the lower surface 12b. Here, the lower surface 11b of the first conductive layer 11 is also the second surface 215b of the composite film 215A, and the upper surface 12a of the second conductive layer 12 is also the first surface 215a of the composite film 215A.
[0102] The first layer 14 is a supporting layer for the first conductive layer 11 and the second conductive layer 12, and includes an insulating material such as a resin. An example of the first layer 14 is a resin layer containing a thermoplastic resin such as polyethylene terephthalate (PET). The first layer 14 has a thickness in the range of 3 μm to 12 μm, preferably in the range of 3 μm to 6 μm (for example, about 4.5 μm). When applied to the positive electrode of a lithium ion secondary battery, the first conductive layer 11 and the second conductive layer 12 can be aluminum films, respectively.
[0103] Figure 4 Schematically Figure 2 The second electrode 220A of this embodiment has a structure that is basically the same as the first electrode 210A, except that the materials constituting each part are different. That is, the second electrode 220A includes: a composite film 225A having a third surface 225a and a fourth surface 225b. The second electrode 220A further includes one or more second material layers 222. Figure 2 In the illustrated structure, the second electrode 220A in the single cell 200A, which is located on the outermost side of the stacked structure of the first electrode 210A and the second electrode 220A, has a second material layer 222 on one side of the third surface 225a and the fourth surface 225b of the composite film 225A. Figure 4 As shown, the second electrode 220A located at another position of the stacked structure of the first electrode 210A and the second electrode 220A includes: a second material layer 222 disposed on the third surface 225a side of the composite film 225A; and a second material layer 222 disposed on the fourth surface 225b side.
[0104] exist Figure 4 In the illustrated structure, the composite film 225A includes: a first conductive layer 21, a second conductive layer 22, and a first layer 24 located between the first conductive layer 21 and the second conductive layer 22. The first conductive layer 21 has: an upper surface 21a located on the first layer 24 side of the surface of the first conductive layer 21; and a lower surface 21b located on the opposite side of the upper surface 21a. The second conductive layer 22 has: a lower surface 22b located on the first layer 24 side of the surface of the second conductive layer 22; and an upper surface 22a located on the opposite side of the lower surface 22b. Figure 4 As shown, here, the lower surface 21b of the first conductive layer 21 is also the fourth surface 225b of the composite film 225A, and the upper surface 22a of the second conductive layer 22 is also the third surface 225a of the composite film 225A. Similar to the composite film 215A of the first electrode 210A, the composite film 225A of the second electrode 220A also has an area (hereinafter referred to as "lead area 220t") where the second material layer 222 is not configured.
[0105] The first layer 24 is a supporting layer for the first conductive layer 21 and the second conductive layer 22, and can be a resin layer containing an insulating material such as polyethylene terephthalate, similarly to the first layer 14 described above. On the other hand, when applied to a lithium ion secondary battery, the first conductive layer 21 and the second conductive layer 22 can be conductive layers formed of copper, respectively.
[0106] As reference Figure 2 As briefly described, the lead 250 is connected to the first electrode 210A, and the lead 260 is connected to the second electrode 220A. The lead 250 on the first electrode 210A side is, for example, an aluminum plate having a thickness of about 100 to 200 μm. On the other hand, the lead 260 on the second electrode 220A side is, for example, a nickel plate having a thickness of about 100 to 200 μm. The "plate" in this specification refers to a self-supporting structure and is not limited to a component having a thickness within a specific range. The "plate" in this specification can include various forms such as foil, sheet, and rod.
[0107] Figure 5 Yes Figure 2 The figure schematically shows a plurality of parts (hereinafter referred to as "third part") including the junction between the second electrode and the lead wire in the structure shown and their surroundings. The lead wire 260 has an upper surface 260a (first surface) and a lower surface 260b (second surface) located on the opposite side of the upper surface 260a. Figure 5 In the illustrated structure, a portion of the upper surface 260 a of the lead 260 faces the fourth surface 225 b located at the bottom of the unit cell 200A among the plurality of second electrodes 220A, and is bonded to the composite film 225A.
[0108] like Figure 5 As schematically shown, one or more third portions 240J are provided between the lead 260 and the stacked body of the plurality of tab regions 220t on the lead 260. Each of the third portions 240J includes one or more bonding portions. Figure 5 The example shown is that the third portion 240J between the second electrode 220A and the lead 260 is provided at a plurality of locations in the lead region 220t. As described later, each third portion 240J includes: one or more joints that electrically and mechanically join the second electrode 220A and the lead 260 to each other by solid phase bonding. In addition, the third portion 240J may also include: an area where a solid phase bond is not formed between the second electrode 220A and the lead 260. In addition, the same connection structure as the second electrode 220A can also be applied between the first electrode 210A and the lead 250 in the single cell 200A. However, in the following description, in order to avoid the description becoming redundant, the details of the connection between the second electrode 220A and the lead 260 are mainly described.
[0109] Figure 6 The appearance of the third part in the laminate of the composite film is schematically shown. Figure 6 As shown, Figure 5 The third portion 240J shown in FIG. 1 has a plurality of recesses 228 formed in the laminated body of the composite film 225A. Figure 6 In the example shown, a plurality of recesses 228 are formed in the laminate of the composite film 225A along the X direction and the Y direction in the figure which are orthogonal to each other.
[0110] Figure 6 This is an example in which a plurality of recesses 228 are formed in the lead region 220t as a connection structure between the lead wire 260 and the plurality of second electrodes 220A. Figure 6 In the illustrated structure, each of the plurality of recesses 228 has an opening 28 a and an inner wall surface 28 c located on the third surface 225 a of the composite film 225A located at the uppermost layer.
[0111] When viewed in the Z direction in the figure, the opening 28a has a roughly rectangular shape. Here, the "rectangle" in this specification is not limited to a quadrilateral in which all corners are strictly right angles, and a shape in which the corners are rounded is also included in the meaning of the "rectangle" in this specification. In addition, the sides of the quadrilateral are not limited to line segments, and can also have undulations. "Having undulations" means, for example, winding with a width within ±30% of the length of the line segment in the orthogonal direction relative to the imaginary line segment that constitutes the side of the rectangle. Or, it means: winding with a width within ±300μm in the orthogonal direction relative to the imaginary line segment that constitutes the side of the rectangle.
[0112] exist Figure 6 In the example shown, the convex portion 28p that protrudes in the positive direction of Z relative to the upper surface 260a of the lead 260 is formed so as to surround the opening 28a. When viewed in the Z direction in the figure, sometimes two convex portions 28p are formed between two adjacent openings 28a, and sometimes one convex portion 28p is formed between two adjacent openings 28a. In the embodiment of the present invention, it is not necessary for the third surface 225a of the composite film 225A to have a convex portion 28p around each opening 28a.
[0113] Figure 7 A portion of the cross section of the third portion between the composite film and the lead is schematically shown. In an actual device, 20 composite films may be connected to the lead, but Figure 7 In order to avoid the drawings becoming too complicated, in the composite film 225A included in the single cell 200A, the bottom layer of the stacked structure of the first electrode 210A and the second electrode 220A (in other words, the layer closest to the lead 260) and the layer located above the first electrode 210A are taken out and illustrated.
[0114] The lead 260 has a plate shape extending on a plane parallel to the XY plane of the figure. Here, the "plate shape" in this specification also includes a shape having undulations in a part and a shape having a concave portion in a part of the surface. Figure 8 It will be Figure 7 The area indicated by the dotted circle in FIG. Figure 8 As shown, the upper surface 260 a of the lead 260 may have at least one recess 61 . Each recess 61 has an opening 61 a located on the upper surface 260 a of the lead 260 .
[0115] The composite film 225A in the single cell 200A is electrically and mechanically connected, for example, to the recess 61 of the lead 260. Here, for the sake of convenience, one of the plurality of composite films 225A included in the stacked structure of the first electrode 210A and the second electrode 220A, which is closest to the lead 260, is referred to as a composite film 225Ak, and one of the layers above the composite film 225Ak is referred to as a composite film 225Ah. In this specification, the composite film 225Ak is sometimes referred to as a "first composite film", and the composite film 225Ah is sometimes referred to as a "second composite film". In this case, the first layer, the first conductive layer, and the second conductive layer of the first composite film are sometimes referred to as "first layer", "first conductive layer", and "second conductive layer", respectively, and the first layer, the first conductive layer, and the second conductive layer of the second composite film are sometimes referred to as "second layer", "third conductive layer", and "fourth conductive layer", respectively.
[0116] First, when focusing on the composite film 225Ak closest to the lead 260 among the plurality of composite films 225A, as shown in FIG. Figure 8 As schematically shown, a portion of the first conductive layer 21 of the composite film 225Ak contacts the lead 260 at a position overlapping the recess 61 in the Z direction of the figure, and is connected to the lead 260. Furthermore, when focusing on the second conductive layer 22 located on the opposite side of the first conductive layer 21 on the first layer 24 of the composite film 225Ak, the second conductive layer 22 is connected to the first conductive layer 21 at a position overlapping the recess 61 in the Z direction of the figure. In other words, in this example, the first conductive layer 21 and the second conductive layer 22 of the composite film 225Ak are connected to the lead 260 at a position overlapping the recess 61 of the lead 260 in the Z direction of the figure. The first conductive layer 21 and the second conductive layer 22 may also be connected to the lead 260 at a position lower than a region of the upper surface 260a of the lead 260 where the recess 61 is not formed.
[0117] At least a portion of the first conductive layer 21 of the second composite film 225Ah is located between the second conductive layer 22 of the composite film 225Ah and the second material layer 222 of the lowermost composite film 225Ak. Figure 8As schematically shown, another part of the first conductive layer 21 of the composite film 225Ah is connected to the second conductive layer 22 of the composite film 225Ak of the lowest layer at a position overlapping with the recessed portion 61 of the lead 260 in the Z direction of the figure. Furthermore, the second conductive layer 22 of the composite film 225Ah is connected to the first conductive layer 21 of the composite film 225Ah at a position overlapping with the recessed portion 61 of the lead 260 in the Z direction of the figure. That is, a conductive path is formed between the first conductive layer 21 and the second conductive layer 22 of the plurality of composite films 225A at a position overlapping with the recessed portion 61 of the lead 260 in the Z direction of the figure.
[0118] like Figure 8 As shown, the upper surface 260a of the lead 260 has: a flat first region R1 opposite to the fourth surface 225b of the bottom composite film 225Ak. Here, in this specification, the first region R1 is "flat" means that the distance from the highest part to the lowest part is within 3% of the thickness of the lead. The thickness of the lead is the distance from the lower surface to the upper surface of the lead in the Z direction. In addition, in this specification, observation from the Z direction (top view) is sometimes referred to as "observation in the normal direction of the first region".
[0119] The upper surface 260a of the lead 260 further has one or more second regions R2. The second region R2 is a region where a bonding interface is formed between the material of the first conductive layer 21 of the composite film 225A and the material of the lead 260. The first region R1 described above can be said to be a region located outside the second region R2.
[0120] When the upper surface 260a has more than one recess 61, as shown in FIG. Figure 8 As shown in the example, the second region R2 may also be located inside each recess 61. Alternatively, as described later, the second region R2 may also include the recess 61. The first region R1 is a region located outside one or more recesses 61 and outside the second region R2. The first region R1 may also include a flat region. Figure 8 As illustrated, when the upper surface 260a has a plurality of recessed portions 61 two-dimensionally arranged along the X and Y directions in the figure, for example, the first region R1 is formed in a grid shape on the upper surface 260a when viewed in the Z direction in the figure.
[0121] When the upper surface 260a of the lead 260 has the recess 61, the third surface 225a of the composite film 225A is recessed toward the lead 260 at least in the portion located on the recess 61. That is, it can be said that the opening 28a of the composite film 225A is a portion of the third surface 225a of the composite film 225A that overlaps with the periphery of the recess 61 (i.e., the opening 61a) in the Z direction.
[0122] exist Figure 8 In the example shown, the upper surface 260a of the lead 260 has two recesses 61 adjacent to each other in the X direction in the figure. In this example, a portion of the first layer 24 of the composite film 225Ak located closest to the lead 260 and located between the two recesses 61 when viewed in the Z direction in the figure (hereinafter referred to as "the first portion 24X") includes a portion whose thickness changes along the X direction in the figure. More specifically, the first portion 24X includes: a portion whose thickness increases as it approaches from one of the two recesses 61 to the other; and a portion whose thickness decreases as it approaches from one of the two recesses 61 to the other. The thickness of the first portion 24X refers to the direction in which a plurality of composite films are stacked (in the Z direction). Figure 7 and Figure 8 In the example of , the distance from the upper surface 21a of the first conductive layer 21 (the surface on the first layer 24 side) to the lower surface 22b of the second conductive layer 22 (the surface on the first layer 24 side) in the direction consistent with the Z direction in the figure.
[0123] The first portion 24X of the first layer 24 in the same composite film 225A may have: a portion of the first layer 24 that overlaps with the second material layer 222 when viewed in the Z direction in the figure (hereinafter referred to as "second portion 24Y", see Figure 7 ) thicker portion. By increasing the thickness of the composite film between two adjacent recesses on the upper surface of the lead, when, for example, shear stress is applied to the composite film, cracking of the composite film starting from the position between the two recesses of the lead can be suppressed. That is, damage to the composite film can be suppressed, and the reliability of the power storage device can be improved.
[0124] exist Figure 8 In the figure, the focus is on the composite film 225Ah above the bottom composite film 225Ak. The second conductive layer 22 of the composite film 225Ah has an upper surface 22a located on the side opposite to the first conductive layer 21. The upper surface 22a of the second conductive layer 22 constitutes the third surface 225a of the composite film 225A. Figure 8 In the illustrated structure, the portion of the upper surface 22a of the second conductive layer 22 that overlaps with the recessed portion 61 of the lead 260 in the Z direction of the figure is located at a position lower than Figure 8 That is, the upper surface 22a of the second conductive layer 22 may have a portion located closer to the lower surface 260b of the lead 260, based on the position of the first region R1 of the upper surface 260a of the lead 260.
[0125] The same connection structure as that of the second electrode 220A can be applied also between the first electrode 210A and the lead 250 in the cell 200A.
[0126] Fig.65 Yes Take out Figure 2 The figure schematically shows a plurality of third parts 140J and their surroundings including the joints between the first electrode and the lead in the structure shown. The lead 250 has an upper surface 250a (first surface) and a lower surface 250b (second surface) located on the opposite side of the upper surface 250a. Fig.65 In the illustrated structure, a portion of the upper surface 250 a of the lead 250 faces one second surface 215 b located at the lowermost side of the unit cell 200A among the plurality of first electrodes 210A, and is bonded to the composite film 215A.
[0127] like Fig.65 As schematically shown, one or more third portions 140J each including one or more bonding portions are provided between the lead 250 and the stacked body of the plurality of tab regions 210t on the lead 250 . Fig.65 The example in which the third portion 140J between the first electrode 210A and the lead 250 is provided at a plurality of locations in the lead region 210t is shown. As described later, each third portion 140J includes one or more joints that electrically and mechanically join the first electrode 210A and the lead 250 to each other by solid phase bonding. In addition, the third portion 140J may include an area where no solid phase bonding is formed between the first electrode 210A and the lead 250.
[0128] Fig.66 The appearance of the third portion 140J in the laminate of the composite film is schematically shown. Fig.66 As shown, Fig.65 The third portion 140J shown in FIG. 1 has a plurality of recesses 218 formed in the laminate of the composite film 215A. Fig.66 In the example shown, a plurality of recessed portions 218 are formed in the laminate of the composite film 215A along the X direction and the Y direction in the figure which are orthogonal to each other.
[0129] Fig.66 This is an example in which a plurality of recesses 218 are formed in the lead region 210t as a connection structure between the lead wire 250 and the plurality of first electrodes 210A. Fig.66 In the illustrated structure, each of the plurality of recesses 218 has an opening 18a located on the first surface 215a of the composite film 215A located on the uppermost layer and four inner wall surfaces 18c. Figure 6 Similarly to the illustrated structure, when viewed in the Z direction in the figure, the opening 18a has a substantially rectangular shape.
[0130] exist Fig.66In the example shown, the convex portion 18p that protrudes in the positive direction Z relative to the upper surface 250a of the lead 250 is formed so as to surround the opening 18a. When viewed in the Z direction in the figure, sometimes two convex portions 18p are formed between two adjacent openings 18a, and sometimes one convex portion 18p is formed between two adjacent openings 18a. In the embodiment of the present invention, it is not necessary for the first surface 215a of the composite film 215A to have the convex portion 18p around each opening 18a.
[0131] Fig.67 A portion of the cross section of the third portion between the composite film and the lead is schematically shown. Figure 8 Similarly, in the composite film 215A included in the cell 200A, the bottom sheet (in other words, the sheet closest to the lead 250 ) of the stacked structure of the first electrode 210A and the second electrode 220A and the upper sheet sandwiching the second electrode 220A are shown.
[0132] The lead 250 has a plate shape extending on a plane parallel to the XY plane in the figure. Fig.67 It also stated that Fig.67 An enlarged view of the area indicated by the dotted circle in FIG. Fig.67 As shown, the upper surface 250 a of the lead 250 may have at least one recess 51 .
[0133] The composite film 215A in the single cell 200A is electrically and mechanically connected, for example, in the recess 51 of the lead 250. Here, for the sake of convenience, one of the plurality of composite films 215A included in the stacked structure of the first electrode 210A and the second electrode 220A, which is closest to the lead 250, is referred to as a composite film 215Ak, and one of the layers above the composite film 215Ak is referred to as a composite film 215Ah. In this specification, the composite film 215Ak is sometimes referred to as a "first composite film", and the composite film 215Ah is sometimes referred to as a "second composite film". In this case, the first layer, the first conductive layer, and the second conductive layer of the first composite film are sometimes referred to as "first layer", "first conductive layer", and "second conductive layer", respectively, and the first layer, the first conductive layer, and the second conductive layer of the second composite film are sometimes referred to as "second layer", "third conductive layer", and "fourth conductive layer", respectively.
[0134] First, when focusing on the composite film 215Ak closest to the lead 250 among the plurality of composite films 215A, as shown in FIG. Fig.67As schematically shown, a portion of the first conductive layer 11 of the composite film 215Ak contacts the lead 250 at a position overlapping the recess 51 in the Z direction of the figure, and is connected to the lead 250. Furthermore, when focusing on the second conductive layer 12 located on the opposite side of the first conductive layer 11 on the first layer 14 of the composite film 215Ak, the second conductive layer 12 is connected to the first conductive layer 11 at a position overlapping the recess 51 in the Z direction of the figure. In other words, in this example, the first conductive layer 11 and the second conductive layer 12 of the composite film 215Ak are connected to the lead 250 at a position overlapping the recess 51 of the lead 250 in the Z direction of the figure. The first conductive layer 11 and the second conductive layer 12 may also be connected to the lead 260 at a position lower than the region where the recess 51 is not formed in the upper surface 250a of the lead 250.
[0135] At least a portion of the first conductive layer 11 of the second composite film 215Ah is located between the second conductive layer 12 of the composite film 215Ah and the first material layer 212 of the bottom composite film 215Ak. Fig.67 As schematically shown, another part of the first conductive layer 11 of the composite film 215Ah is connected to the second conductive layer 12 of the composite film 215Ak of the lowest layer at a position overlapping with the recessed portion 51 of the lead 250 in the Z direction of the figure. Furthermore, the second conductive layer 12 of the composite film 215Ah is connected to the first conductive layer 11 of the composite film 215Ah at a position overlapping with the recessed portion 51 of the lead 250 in the Z direction of the figure. That is, a conductive path is formed between the first conductive layer 11 and the second conductive layer 12 of the plurality of composite films 215A at a position overlapping with the recessed portion 51 of the lead 250 in the Z direction of the figure.
[0136] like Fig.67 As shown, the upper surface 250a of the lead 250 has a flat first region R1 that is opposite to the second surface 215b of the lowermost composite film 215Ak. The upper surface 250a of the lead 250 also has one or more second regions R2 each including a recess 51. Here, the second region R2 is a region where a bonding interface is formed between the material of the first conductive layer 11 of the composite film 215A and the material of the lead 250. The first region R1 can be said to be a region located outside the second region R2.
[0137] When the upper surface 250a has more than one recess 51, as shown in FIG. Fig.67 As shown in the example, the second region R2 may also be located inside each concave portion 51. Alternatively, as described later, the second region R2 may also include the concave portion 51. The first region R1 is a region located outside one or more concave portions 51 and outside the second region R2. The first region R1 may also include a flat region. Fig.67As illustrated, when the upper surface 250a has a plurality of recessed portions 51 two-dimensionally arranged along the X and Y directions in the figure, for example, the first region R1 is formed in a grid shape on the upper surface 250a when viewed in the Z direction in the figure.
[0138] When the upper surface 250a of the lead 250 has the recess 51, the upper surface 215a of the composite film 215A is recessed toward the lead 250 at least in the portion located on the recess 51. That is, it can be said that the opening 18a of the composite film 215A is a portion of the upper surface 215a of the composite film 215A that overlaps with the periphery of the recess 51 (i.e., the opening 51a) in the Z direction.
[0139] exist Fig.67 In the example shown, the upper surface 250a of the lead 250 has two recesses 51 adjacent to each other in the X direction in the figure. In this example, a portion of the first layer 14 of the composite film 215Ak located closest to the lead 250 and located between the two recesses 51 when viewed in the Z direction in the figure (hereinafter referred to as "the first portion 14X") includes a portion whose thickness changes along the X direction in the figure. More specifically, the first portion 14X includes: a portion whose thickness increases as it approaches from one of the two recesses 51 to the other; and a portion whose thickness decreases as it approaches from one of the two recesses 51 to the other. The thickness of the first portion 14X refers to the direction in which a plurality of composite films are stacked (in the Z direction). Fig.67 In the example, the distance from the upper surface 11a of the first conductive layer 11 (the surface on the first layer 14 side) to the lower surface 12b of the second conductive layer 12 (the surface on the first layer 14 side) in the direction consistent with the Z direction in the figure.
[0140] The first portion 14X of the first layer 14 in the same composite film 215A may have a portion having a greater thickness than a portion of the first layer 14 that overlaps with the first material layer 212 when viewed in the Z direction in the figure (hereinafter referred to as "the second portion 14Y"). By increasing the thickness of the composite film between two adjacent recesses on the upper surface of the lead, when, for example, shear stress is applied to the composite film, the occurrence of cracks in the composite film starting from the position between the two recesses of the lead can be suppressed. That is, the effect of suppressing damage to the composite film and improving the reliability of the storage device can be obtained.
[0141] exist Fig.67 In the figure, the focus is on the composite film 215Ah above the bottom composite film 215Ak. The second conductive layer 12 of the composite film 215Ah has an upper surface 12a located on the opposite side to the first conductive layer 11. The upper surface 12a of the second conductive layer 12 constitutes the first surface 215a of the composite film 215A. Fig.67In the illustrated structure, the portion of the upper surface 12a of the second conductive layer 12 that overlaps with the recessed portion 51 of the lead 250 in the Z direction of the figure is located at a position lower than Fig.67 That is, the upper surface 12a of the second conductive layer 12 may have a portion located closer to the lower surface 250b of the lead 250, based on the position of the first region R1 of the upper surface 250a of the lead 250.
[0142] The connection structure between the first electrode and the lead wire and the connection structure between the second electrode and the lead wire are described in more detail. The connection structure between the first electrode and the lead wire is described below as an example, but the same connection structure can also be applied to the second electrode.
[0143] Fig. 9 This is a diagram showing a microscope image of a cross section of a recessed portion formed on the upper surface of a lead and its surroundings as a line graph. Fig. 9 This is an example of a structure in which a total of nine composite films are connected to the lead wires.
[0144] exist Fig. 9 In the example shown, the upper surface 260a of the lead 260 has two concave portions 61 adjacent to each other along the X direction in the figure. The portion of the laminate of the composite film 225A located between the two concave portions 61 of the lead 260 bulges in the positive direction of Z in the figure. In contrast, in the laminate of the composite film 225A, the thickness of the laminate as a whole becomes smaller in the portion overlapping with the concave portion 61 when viewed in the Z direction in the figure. As a result, a concave portion 228 (see FIG. 2 ) is formed in the portion of the laminate of the composite film 225A that overlaps with the concave portion 61 when viewed in the Z direction in the figure. Figure 6 ).
[0145] like Fig. 9 As schematically shown, in the laminate of the composite film 225A, the region of the upper surface 260a of the lead 260 overlapping with the second region R2 includes a joint 25 formed by connecting the first conductive layer 21 and the second conductive layer 22 of the plurality of composite films 225A. The joint 25 includes the material of the first conductive layer 21 and the material of the second conductive layer 22. When viewed in the Z direction in the figure, the joint 25 includes at least a portion located inside the recess 61. However, the joint 25 may also include a portion located outside the recess 61 when viewed in the Z direction in the figure.
[0146] In the embodiment of the present invention, it is not necessary for the plurality of composite films to be selectively connected to the lead only at the position of the concave portion on the upper surface side of the lead. The plurality of composite films can be bonded to the lead at least at the position overlapping with the concave portion on the upper surface side of the lead in the stacking direction of the plurality of composite films. For example, the composite film closest to the lead among the plurality of composite films may be connected to the lead in the entire second region R2.
[0147] like Fig. 9 As shown schematically, the joint 25 may contain a resin 24r therein. The resin 24r may be a resin contained in the first layer 24 of any one of the plurality of composite films 225A connected to the lead 260. By including the resin 24r in the joint 25, the convex portion 28p can be suppressed to be lower. In addition, compared with the case where the joint 25 is composed only of a metal-metal joint, in the case of a joint of different types of materials including metal-resin-metal, there is also a case where the joint strength becomes higher. Moreover, the resin 24r is closely attached to the conductive layer of the joint 25 due to its viscosity, thereby suppressing the peeling of the conductive layer of the joint 25, and can further improve the joint reliability of the joint 25.
[0148] As in Fig. 9 As schematically shown in the enlarged view in FIG. 1 , the resin 24r is located at a portion overlapping with the recessed portion 61 of the lead 260 when viewed in the Z direction in the figure, and may be located at a position deeper in the Z direction in the figure than the first region R1 of the upper surface 260a of the lead 260. In other words, the resin 24r may be located closer to the lower surface 260b in the Z direction in the figure, with reference to the position of the first region R1 of the upper surface 260a.
[0149] exist Fig. 9 In the illustrated structure, the lead 260 has a recess 62A on the lower surface 260b in addition to the recess 61 on the upper surface 260a. Fig. 9 In the examples shown, the recess 62A is located approximately directly below one of the recesses 61 on the upper surface 260a side. In other words, in these examples, the recess 62A is formed in the lower surface 260b at a position overlapping with one of the recesses 61 when viewed in the Z direction in the figure. The recess 62A is, for example, a portion of the lower surface 260b that is located closer to the upper surface 260a than the flat third region R3. The "flat area" of the lower surface 260b of the lead 260 is an area where the distance from the highest part to the lowest part is within 3% of the thickness of the lead. When viewed in the Z direction in the figure, the third region R3 may at least partially overlap with the first region R1 of the upper surface 260a.
[0150] The shape and arrangement of the recessed portions formed on the lower surface side of the lead (i.e., the side not in contact with the composite film) are not limited to Fig. 9 Example shown. Fig.10 This is a schematic diagram showing another example of a microscope image of a cross section of a laminate of a composite film and a lead wire using a line graph. Fig.10In the illustrated structure, the lower surface 260b of the lead 260 has a recess 62B. When viewed in the Z direction in the figure, the recess 62B is located between two recesses 61 adjacent to each other along the X direction in the figure. In other words, the recess 62B is located on the opposite side of the first region R1 of the upper surface 260a of the lead 260. The first region R1 may also be curved in a convex shape. Fig.10 This is an enlarged view and is not shown in the figure, but the other first region in the upper surface 260a of the lead 260 may also include a flat region. The flat region can be confirmed by a microscope image of the laminated body of the composite film. Fig.10 In FIG. 1 , a virtual surface (reference surface) S1 based on the flat region is indicated by a dotted line. The above-mentioned recessed portion 61 is a portion of the upper surface 260 a located closer to the lower surface 260 b than the surface S1.
[0151] The shape of the recessed portion on the lower surface side of the lead and their arrangement are not limited to Fig. 9 and Fig.10 The shapes and configurations illustrated may be various shapes and configurations. When viewed in the Z direction in the figure, the lower surface 260b of the lead 260 may also have: a recess 62A located at a position overlapping with one of the recesses 61 on the upper surface 260a side, and a recess 62B located between two adjacent recesses 61.
[0152] The recessed portion on the upper surface side of the lead may also have various shapes. The bottom of the recessed portion 61 may also include a flat area in part. Fig.10 In the example shown, the left side of the two concave portions 61 adjacent to each other along the X direction in the figure includes a flat portion on a portion of the bottom. In this specification, the bottom of the concave portion 61 is "flat" when the distance from the highest part to the lowest part of the surface of the bottom of the concave portion 61 is within 3% of the thickness of the lead.
[0153] Fig.11 An example of the cross-sectional shape of the composite film connected to the lead is schematically shown. Fig.11 : shows a part of the cross section of the lead 260 and the composite film 225A when cut along a plane perpendicular to the first region R1 of the upper surface 260a of the lead 260. In addition, here, in order to avoid making the drawing too complicated, one of the bottom layers of the plurality of composite films 225A connected to the lead 260, which is closest to the lead 260, is taken out for illustration.
[0154] like Fig.11 As shown, the cross section of the portion of the composite film located between two adjacent recesses 61 may be in a shape showing multiple bends. Fig.11In the illustrated structure, the composite film 225A has a mutually folded portion 225f between two concave portions 61 adjacent to each other in the X direction in the figure. Fig.11 In the illustrated structure, the composite film 225A has a portion 225f that overlaps with itself in the Z direction in the figure.
[0155] In a typical embodiment of the present invention, the portion of the composite film 225A located between two adjacent recesses 61 is separated from the first region R1 sandwiched by the two recesses 61 in the upper surface 260a of the lead 260. In other words, the portion of the composite film 225A located between two adjacent recesses 61 is not connected to the first region R1. If the composite film 225A has a mutually folded portion 225f between two adjacent recesses 61, for example, when the lead 260 is subjected to an external force, the occurrence of cracks in the composite film 225A starting from the portion located between the two adjacent recesses 61 can be suppressed. That is, the same effect as if the thickness of the composite film 225A is increased can be obtained. In addition, a portion of the composite film 225A may also be in contact with the first region R1.
[0156] Fig.12 Another example of the cross-sectional shape of the composite film connected to the lead is schematically shown. Fig.12 As schematically shown, one or both of the first conductive layer 21 and the second conductive layer 22 of the composite film 225A may be in a shape that is bent in a cross-sectional view.
[0157] exist Fig.12 In the illustrated structure, the first conductive layer 21 of the composite film 225A has a curved arc portion 21s between two concave portions 61 adjacent to each other in the X direction in the figure. When focusing on a portion 21as located in the arc portion 21s in the upper surface 21a of the first conductive layer 21, the portion 21as is curved in a direction away from the lead 260 in the cross-sectional view. The upper surface 21a of the first conductive layer 21 is a surface on the opposite side of the lower surface 21b of the lead 260 that is opposite to the first region R1. The upper surface 21a can also be said to be a surface of the composite film 225A located on the opposite side of the lead 260 when focusing on the first conductive layer 21.
[0158] The term "curved" in this specification means a shape having a greater curvature in a cross-sectional view than an arc connecting the centers of two adjacent recesses 61. In addition, the term "arc-shaped" in the present invention means a curved line in a cross-sectional view, and is not limited to a bow-shaped shape or an arc-shaped shape.
[0159] Fig.13 Another example of the cross-sectional shape of the composite film connected to the lead wire is schematically shown. Fig.13In the illustrated structure, the first conductive layer 21 of the composite film 225A has two arc-shaped portions 21t that are bent between two concave portions 61 that are adjacent to each other in the X direction in the figure. Fig.13 In the example shown, the first conductive layer 21 includes an arcuate portion 21t that is bent back from the +X direction in the figure toward the -X direction, and an arcuate portion 21t that is bent back from the -X direction in the figure toward the +X direction. That is, in this example, the first conductive layer 21 includes a bent portion 21f that is folded by bending and overlapped in the Z direction in the figure between two concave portions 61 that are adjacent to each other in the X direction in the figure.
[0160] exist Fig.13 In the example shown, when the first conductive layer 21 has a folded portion, the effective thickness of the first layer 24 along the Z direction in the figure is obtained by adding the thickness of the two portions overlapping in the Z direction in the figure. The first conductive layer 21 has a folded portion between the two recesses 61, and thus, the composite film 225A as a whole includes the folded portion (see Fig.11 ) Similarly, even when shear stress acts on the composite film 225A, it is possible to expect an effect of suppressing the occurrence of cracks in the composite film 225A starting from the position between the two recessed portions 61.
[0161] Similar to the first conductive layer 21 , the second conductive layer 22 may have a shape that is bent in a cross-sectional view. Fig.14 Another example of the cross-sectional shape of the composite film connected to the lead wire is schematically shown. Fig.14 In the illustrated example, the second conductive layer 22 of the composite film 225A has a curved arc-shaped portion 22 s between two concave portions 61 adjacent to each other in the X direction in the figure.
[0162] exist Fig.14 In the illustrated structure, the arc-shaped portion 22s of the second conductive layer 22 is bent in a direction away from the lead 260, and a portion 22as of the upper surface 22a of the second conductive layer 22 located in the arc-shaped portion 22s also has a shape that conforms to the shape of the second conductive layer 22. That is, the portion 22as has a shape that is bent in a direction away from the lead 260 in a cross-sectional view. Here, the upper surface 22a is a surface located on the opposite side of the lower surface 21b of the first conductive layer 21 with respect to the first layer 24 of the composite film 225A.
[0163] exist Fig.14In the illustrated structure, the second conductive layer 22 further has a folded portion 22f that overlaps each other in the Z direction of the figure by bending and folding each other between the two recesses 61. The folded portion 22f includes an arcuate portion 22t that folds back from the -X direction of the figure toward the +X direction, and an arcuate portion 22t that folds back from the +X direction of the figure toward the -X direction in the opposite direction.
[0164] Between the two recessed portions of the lead wire, a conductive film such as a conductive film is introduced between the two closest composite films among the stacked composite films. Fig.11 The entangled structure shown can produce mechanical engagement between two composite films. By producing a cross-sectional shape that meshes with each other between multiple composite films, a structure that can be integrated with multiple composite films between two recesses of the lead can be formed. Thus, the peeling and / or cracking of the composite film from the lead can be suppressed. The cross-sectional shape that meshes with each other between multiple composite films can help improve the reliability of the storage device.
[0165] Fig.15 The connection between the bottommost composite film and the lead in the composite film stack is taken out and enlarged. Fig.15 As schematically shown, when focusing on a portion of the composite film 225A that is connected to the recessed portion 61 of the lead 260 , the bonding portion 25 is formed on the composite film 225A.
[0166] In the joint 25, the first conductive layer 21 and the second conductive layer 22 are connected to each other, thereby forming a conductive path therebetween. When the first conductive layer 21 and the second conductive layer 22 are made of a common material, a clear boundary may not be confirmed between the first conductive layer 21 and the second conductive layer 22. Fig.15 As shown, when the joint 25 has a resin 24r therein, the approximate position of the boundary between the first conductive layer 21 and the second conductive layer 22 can be estimated from the position of the resin 24r in the depth direction (here, the Z direction in the figure).
[0167] When the first conductive layer 21 and the lead are made of a common material, a clear boundary may not be confirmed between them. However, for example, when the resin 24r is confirmed to exist at a position deeper than the first region R1 on the upper surface of the lead, it can be concluded that a recess is formed on the upper surface of the lead. Figure 8 As in the example described, if the upper surface of the second conductive layer is such that the portion overlapping with the recessed portion of the lead in the Z direction in the figure includes a portion located closer to the lower surface side of the lead when the position of the first region R1 of the upper surface of the lead is used as a reference, then it can be said that a recessed portion is formed on the upper surface of the lead.
[0168] The bonding portion 25 may have a smaller thickness than other portions of the composite film 225A (e.g., a portion overlapping the second material layer 222 in the stacking direction). In this case, when the composite film 225A is taken out as a single unit, it can be said that the composite film 225A has a concave portion 63 (see FIG. 1 ) that is concave toward the lead 260 on the third surface 225a (i.e., the surface opposite to the lead 260). Fig.15 The recessed portion 63 of the composite film 225A is located at a position corresponding to the recessed portion 61 on the upper surface 260 a of the lead 260 (for example, directly above the recessed portion 61 ).
[0169] exist Fig.15 In the figure, the thickness of the portion of the composite film 225A that overlaps with the recessed portion 61 of the lead 260 in the Z direction in the figure is indicated by a double-headed arrow H1. Here, the length indicated by the double-headed arrow H1 is the distance from the deepest position 61z in the welding interface between the composite film 225A and the lead 260 to the position where the straight line z1 is extended along the Z direction in the figure and intersects with the upper surface 22a of the second conductive layer 22. In addition, the upper surface 22a of the second conductive layer 22 refers to the surface of the second conductive layer 22 located on the side opposite to the lead 260, and constitutes the third surface 225a of the composite film 225A.
[0170] like Figure 11 to Figure 14 As shown, the composite film 225A connected to the lead 260 may have a shape that bulges away from the lead 260 between the two recesses 61 of the lead 260. Fig.15 In the figure, a double arrow H2 indicates the distance in the Z direction in the figure from the position farthest from the lead 260 in the portion of the upper surface 22a of the second conductive layer 22 overlapping with the first region R1 of the lead 260 in the Z direction in the figure to the lead 260. When the distance H2 is compared with the above-mentioned distance H1, in the embodiment of the present invention, the relationship of H1<H2 is established.
[0171] As mentioned above, in Figures 9 to 15 In the embodiment described above, the example of the connection structure with the lead wire is described by taking the second electrode as an example, but the same connection structure can be applied to the first electrode. An example of the connection structure of the first electrode is shown in the schematic diagram based on the microscope image of the embodiment described later (for example Fig.60 etc.)
[0172] Fig.16 An example of the shape and arrangement of the recessed portions formed on the upper surface of the lead is schematically shown. Fig.16 This is equivalent to connecting lead 260 from Figure 1 The second electrode group of the cell 200A shown is separated and is a plan view of the third portion 240J viewed along the normal direction of the upper surface 260 a of the lead 260 .
[0173] exist Fig.16 In the illustrated structure, the upper surface 260a of the lead 260 has a total of 35 recesses 61 arranged two-dimensionally along the X direction and the Y direction in the figure. In this example, the plurality of recesses 61 are formed on the upper surface 260a of the lead 260 in such a way that the centers of the recesses 61 are approximately located at the grid points of the rectangular grid. The configuration of the plurality of recesses 61 is of course not limited to this example. The plurality of recesses 61 may also be arranged two-dimensionally along the first axis and the second axis that is at an acute angle or an obtuse angle relative to the first axis in a plane parallel to the XY plane in the figure.
[0174] By connecting the lead wire and the composite film to each other at multiple locations arranged two-dimensionally, the connection between them can be made stronger. In addition, even if an external force acts on the lead wire, the stress is dispersed at multiple locations, so that the lead wire can be prevented from falling off the composite film. That is, the reliability of the power storage device can be improved.
[0175] Each recess 61 has an opening 61a located on the upper surface 260a of the lead 260. Fig.16 In the illustrated structure, the opening 61a of the recessed portion 61 has a rectangular shape. As described later, the shape of the opening 61a of the recessed portion 61 when viewed in the Z direction in the figure is not limited to a rectangular shape.
[0176] Focus on two openings adjacent to each other along the X or Y direction in the figure, for example, Fig.16 In the figure, attention is paid to the openings 61a of the recess 61P and the recess 61Q adjacent to each other along the X direction in the figure among the plurality of recesses 61. The two openings are arranged along the X direction in the figure across the first region R1 of the upper surface 260a of the lead 260.
[0177] In this example, the width X1 of the opening 61a of one of the two recesses, namely the recess 61P, in the X direction is greater than the distance D1 from the opening 61a of the recess 61P to the opening 61a of the recess 61Q. Here, the width X1 of the opening 61a refers to the maximum value of the width of the opening 61a in a certain direction (here, the X direction in the figure), and the distance D1 between the openings 61a refers to the minimum value of the distance between the openings 61a in the direction.
[0178] By increasing the width X1 of the opening 61a of the recess 61P in the X direction, for example, the bonding interface between the composite film 225A and the lead 260 can be enlarged. By enlarging the bonding interface between the composite film 225A and the lead 260, the effect of reducing the connection resistance between the composite film 225A and the lead 260 can be obtained. In addition, the effect of improving the bonding strength between the composite film 225A and the lead 260 in each recess 61 can also be expected. From the viewpoint of obtaining low connection resistance and high bonding strength, it is advantageous to make the width X1 larger than the distance D1 between the openings 61a.
[0179] On the contrary, Fig.17 As shown, the width X1 of the opening 61a of the recess 61P in the X direction may be smaller than the distance D1 from the opening 61a of the recess 61P to the opening 61a of the recess 61Q. When the shape and configuration of the recess 61 make the distance D1 between the openings 61a larger than the width X1 of the opening 61a, it becomes easier to connect more composite films 225A to the lead 260. That is, the shape and configuration of the recess 61 that satisfies the condition X1<D1 is conducive to the structure of connecting more composite films 225A to the lead 260. Alternatively, the width X1 of the opening 61a of the recess 61P may be the same as the distance D1 between the openings 61a. As described above, the shape of each recess 61 and the configuration of these recesses 61 are not limited to a specific combination.
[0180] It is not necessary in the embodiment of the present invention to make the width of the opening 61a (for example, the width in the X direction in the figure) uniform among the plurality of recesses 61. In addition, it is not necessary to make the distance between the openings 61a of two adjacent recesses 61 in the X direction in the figure uniform among the plurality of recesses 61.
[0181] exist Fig.16 In the example shown, the plurality of recesses 61 include, in addition to the above-described set of recesses 61P and recesses 61Q, a recess 61R adjacent to the recess 61Q on the side opposite to the recess 61P along the X direction in the figure. When the distance from the opening 61a of the recess 61Q to the opening 61a of the recess 61R along the X direction in the figure is set to D2, the distance D2 may be different from the distance D1 from the opening 61a of the recess 61P to the opening 61a of the recess 61Q.
[0182] In this way, the recesses 61 may be evenly distributed in the bonding portion (part 3) or unevenly distributed. For example, the intervals between the recesses 61 may be randomly changed. Or, for example, in part 3, the arrangement pitch of the recesses 61 may be changed in stages. By making the distribution of the recesses 61 uneven, the recesses 61 can have a density distribution. Thus, for example, within part 3, the bonding strength with the composite film can be distributed. In addition, by configuring the recesses 61, the flow of the resin of the composite film bonded to the lead 260 can be controlled. Furthermore, by changing the intervals between the recesses 61, the convex portions ( Figure 8 The height of the protrusion 28p) has a distribution.
[0183] exist Fig.16In the example shown, the plurality of recesses 61 further include a group of recesses 61S and recesses 61T adjacent to each other along the X direction in the figure. When the distance from the opening 61a of the recess 61S to the opening 61a of the recess 61T along the X direction in the figure is set to D3, the distance D3 may be different from at least one of the distance D1 and the distance D2 described above.
[0184] exist Fig.16 and Fig.17 In the figure, the opening 61a is depicted in a shape close to a square. However, this is only for the convenience of explanation. The shape of the opening 61a when observed in the stacking direction of multiple composite films (here, the Z direction in the figure) can be a deformed quadrilateral, a quadrilateral including a partially curved side, etc. The quadrilateral "having a deformation" means that part or all of the vertices of the quadrilateral deviate from the vertices of the ideal shape (rectangle). The distance between the vertices of the deformed quadrilateral and the vertices of the ideal rectangle can be, for example, within 30% of the length of the sides constituting the rectangle. Alternatively, the distance between the vertices of the deformed quadrilateral and the vertices of the ideal rectangle can also be, for example, within 300μm. Here, the shape of the opening 61a can be determined based on the shape of the boundary between the first region R1 of the upper surface 260a of the lead 260 and a portion of the upper surface 260a that is located lower than the first region R1 in the stacking direction of the composite film.
[0185] In the embodiment of the present invention, it is not necessary for the sizes (e.g., the area when viewed along the Z direction in the figure) of the plurality of recesses 61 formed on the upper surface 260a of the lead 260 to be strictly the same. For example, the width of the opening 61a in the X direction in the figure or the width of the opening 61a along the Y direction in the figure may be different between adjacent recesses 61P and recesses 61Q. In other words, the third portion 240J may include a plurality of recesses 61 having different widths of the opening 61a along the X direction or the Y direction in the figure.
[0186] Furthermore, it is not necessary for the multiple recesses 228 formed in the laminate of the composite film 225A to have the same size. The multiple recesses 228 may include recesses 228 having openings 28a with different widths along the X direction or the Y direction in the figure.
[0187] Fig.18 An example of a plurality of recessed portions that can be formed in a laminate of a composite film is shown. Fig.18In the example shown, a plurality of recesses 228 are formed on the laminate of the composite film 225A, which are arranged two-dimensionally along the X direction and the Y direction in the figure. The plurality of recesses 228 each have a shape that is recessed toward the lead 260. In this example, the plurality of recesses 228 each have a shape that includes four inner wall surfaces 28c. The plurality of recesses 228 are formed on the third surface 225a of the composite film 225A at positions corresponding to the plurality of recesses 61 of the lead 260 (for example, directly above).
[0188] exist Fig.18 In the example shown, the plurality of recesses 228 include a recess 228P and a recess 228Q adjacent to each other along the X direction in the figure. In this example, the width X7 of the opening 28a of one of the two recesses, namely the recess 228P, in the X direction is greater than the distance D5 from the opening 28a of the recess 228P to the opening 28a of the recess 228Q. Here, the width X7 of the opening 28a refers to the maximum value of the width of the opening 28a in a certain direction (here, the X direction in the figure), and the distance D5 between the openings 28a refers to the minimum value of the distance between the openings 28a in the direction.
[0189] A large width X7 of the opening 28a of the recess 228P means a relatively large bonding interface between the composite film 225A and the lead 260. That is, the shape and arrangement of the recess 228 satisfying the condition X7>D5 can be expected to reduce connection resistance or improve bonding strength.
[0190] Fig.19 Another example of a plurality of recessed portions that can be formed in a laminate of a composite film is schematically shown. Fig.18 The example shown is the opposite, Fig.19 As shown, the relationship X7<D5 can also be established. The shape and arrangement of the recessed portion 228 that establishes the relationship X7<D5 is advantageous for connecting a larger number of composite films 225A to the lead wire 260 .
[0191] exist Fig.18 In the illustrated structure, the plurality of recesses 228 further include a recess 228R adjacent to the recess 228Q on the side opposite to the recess 228P along the X direction in the figure. When the distance from the opening 28a of the recess 228Q to the opening 28a of the recess 228R along the X direction in the figure is set to D6, the distance D6 may be different from the distance D5 from the opening 28a of the recess 228P to the opening 28a of the recess 228Q.
[0192] exist Fig.18In the example shown, the plurality of recesses 228 also includes a group of recesses 228S and recesses 228T adjacent to each other along the X direction in the figure. When the distance from the opening 28a of the recess 228S to the opening 28a of the recess 228T along the X direction in the figure is set to D7, the distance D7 may be different from at least one of the distance D5 and the distance D6 described above.
[0193] In this way, the same relationship as "between the width of the recess 61 formed on the upper surface 260a of the lead 260 and the distance between the two recesses 61" can also be established as "between the width of the recess 228 formed on the third surface 225a of the composite film 225A and the distance between the two recesses 228". It is not necessary in the embodiment of the present invention that the width of the opening 28a (for example, the width in the X direction in the figure) is consistent among multiple recesses 228. In addition, it is not necessary to make the distance between the openings 28a of two adjacent recesses 228 in the X direction in the figure consistent among multiple recesses 228. Regarding the distance between the two recesses 228, the distance between the centers of the two recesses 228 may be used instead of the distance between the openings 28a. In addition, in Fig.18 and Fig.19 , the opening 28a is depicted in a shape close to a square. However, this is only for the sake of convenience, and the shape of the opening 28a when viewed in the stacking direction of the plurality of composite films (here, the Z direction in the figure) may be a skewed quadrilateral, a quadrilateral including a partially curved side, or the like.
[0194] Fig. 20 An enlarged view of one of the plurality of recesses that can be formed in a laminate of a composite film. Fig. 20 In the example shown, the convex portion 28p located around the rectangular opening 28a is a structure formed by the third surface 225a of the composite film 225A protruding. Fig. 20 In the example shown, the bottom surface 28b of the recessed portion 228 has a rectangular shape. The shape of the recessed portion 228 itself formed in the laminated body of the composite film 225A is of course not limited to Fig. 20 The shapes of the bottom surface 28b and the opening 28a of the recess 228 are not limited to rectangles.
[0195] Fig.21 Still another example of the shape and arrangement of the recessed portion formed on the upper surface of the lead is schematically shown. Fig.21 This can also be regarded as an example in which a plurality of recessed portions 61 each having a rectangular opening 61a are arranged relatively sparsely. Fig.21 In the illustrated structure, the center of each recess 61 is located at a lattice point of the triangular lattice.
[0196] exist Fig.21In the example shown, the plurality of recesses 61 are arranged two-dimensionally along the X direction in the figure and a direction different from both the X direction and the Y direction. Fig.21 In the example shown, it can be said that the opening 61 a of each recess 61 has a shape whose width changes along the X direction and the Y direction in the figure.
[0197] In this example, the plurality of recesses 61 are arranged two-dimensionally along a direction at +45° (hereinafter referred to as the "+45° direction") and a direction at -45° (hereinafter referred to as the "-45° direction") relative to the X direction in the figure. If we focus on two recesses 61 adjacent to each other in the -45° direction, the width S1 of one opening 61a of the two recesses in the -45° direction and the distance E1 between the openings 61a of the two recesses satisfy the relationship S1<E1. Fig.16 Similarly to the example described above, the shape and arrangement of the recessed portion 61 may be adopted so that the relationship S1>E1 holds.
[0198] Fig. 22 Indicates that it can be formed with Fig.21 The recessed portion 61 shown is an example of the shape of a plurality of recessed portions of a composite film for wire connection. Fig. 22 This corresponds to a plan view of the laminated body of the composite film 225A on the lead 260 as viewed from the third surface 225a side of the composite film 225A located in the uppermost layer.
[0199] Fig. 22 This is an example in which two composite films 225A are connected to the lead wire 260. In any example, a plurality of recessed portions 228 each having a rectangular opening 28a is formed on the third surface 225a of the composite film 225A located on the uppermost layer.
[0200] exist Fig. 22 In the example shown, the plurality of recesses 228 are arranged two-dimensionally along the +45° direction and the -45° direction. If attention is paid to two recesses 228 adjacent to each other in the -45° direction, in this example, the width S7 of the opening 28a of one of the two recesses in the -45° direction and the distance E7 between the openings 28a of the two recesses in the -45° direction satisfy the relationship S7>E7. Conversely, the relationship S7<E7 may also satisfy.
[0201] Here, the set of recesses 228 is arranged in a rectangular region as a whole, thereby forming one third part 240J. The third part 240J includes a plurality of recesses 228 in a rectangular region of, for example, 3 mm×4 mm. However, the shape of each third part 240J is not limited to a rectangle. For example, the set of recesses 228 may be arranged in a circular region as a whole to form one third part 240J. In other words, the shape of each third part 240J may also be a circular shape or the like.
[0202] Fig.23 Enlarge Fig. 22 In this example, the inner wall surface 28c of the recess 228 has a plurality of steps. Thus, it is not necessary for the inner wall surface 28c defining the shape of the recess 228 to be a flat surface. The inner wall surface and / or the bottom surface defining the shape of the recess 228 may also have a shape with steps or the like.
[0203] Fig.24 Still another example of the shape and arrangement of the recessed portion formed on the upper surface of the lead is schematically shown. Fig.25 Schematically Fig.24 A partial cross section of the structure shown. Fig.24 In the example shown, the recessed portion 61 has a strip-like plan view shape that is longer in the Y direction than in the X direction in the figure.
[0204] exist Fig.24 In the example shown, the width X1 of the opening 61a of the recess 61 in the X direction is smaller than the width Y1 in the Y direction. By forming the bonding portion 25 in a strip shape, the bonding between the lead and the composite film can be made stronger than when the bonding portion 25 is formed in a dot shape. Fig.24 and Fig.25 As schematically shown, the width X1 of the opening 61a of the concave portion 61 in the X direction and the distance D1 between the openings 61a of two concave portions 61 adjacent to each other in the X direction in the figure satisfy the relationship D1>X1. Conversely, the width X1 of the opening 61a and the distance D1 between the openings 61a may satisfy the relationship D1<X1.
[0205] Fig.26 Schematically showing that a Fig.24 An example of the shapes of the multiple recesses of the composite film with the lead wires of the recesses shown. In this example, the multiple recesses 228 formed in the laminated body of the composite film 225A each have a strip-shaped top view shape that is longer in the Y direction than in the X direction in the figure. The width X7 of the opening 28a of the recess 228 in the X direction may be smaller than the width Y7 in the Y direction. In addition, in this example, the distance D7 between the openings 28a of two recesses 228 adjacent to each other in the X direction in the figure is larger than the width X7 of the opening 28a in the X direction. Conversely, the relationship D7<X7 may also be established.
[0206] Fig. 27 Another example of the shape and arrangement of the recessed portion formed on the upper surface of the lead is schematically shown. Fig. 27 As shown in the example, the recessed portion 61 may have a plan view shape that is longer in the X direction than in the Y direction in the figure. Fig. 27In the example shown, the relationship X1>Y1 holds. Fig. 27 In the figure, if the distance along the Y direction between the openings 28a of two adjacent concave portions 228 in the Y direction is set as D4, the relationship D4>Y1 is established between the distance D4 and the width Y1 in the Y direction of the opening 61a of the concave portion 61. Conversely, the relationship D4<Y1 may also be established.
[0207] Fig.28 Schematically showing that a Fig. 27 An example of the shape of multiple recesses in a composite film in which the lead wires of the recesses are connected is shown. Fig.28 In the example shown, the recess 228 has a plan view shape that is longer in the X direction than in the Y direction in the figure. Fig.28 In the example shown, the relationship X7>Y7 is established between the width X7 of the opening 28a of the concave portion 228 in the X direction and the width Y7 in the Y direction. In this example, the relationship D10>Y7 is established between the distance D10 along the Y direction between the openings 28a of two adjacent concave portions 228 and the width Y7 of the opening 28a in the Y direction. Conversely, the relationship D10<Y7 may also be established.
[0208] Fig.29 Another example of the shape and arrangement of the recess formed on the upper surface of the lead is schematically shown. In the embodiment of the present invention, it is not necessary for the recess 61 to extend in a direction parallel to or perpendicular to one side of the lead region. Fig.29 As shown, the extending direction of the recess 61 may be inclined relative to one side of the tab region. By inclining the extending direction of the bonding portion 25 relative to the direction in which the composite film is prone to cracking, the effect of suppressing the occurrence of cracks in the composite film can be expected.
[0209] In this example, with reference Fig.21 Similarly to the example described above, the width S1 in the -45° direction of the opening 61a of one of the two concave portions 61 adjacent to each other in the -45° direction and the distance E1 between the openings 61a of the two concave portions satisfy the relationship S1<E1. Conversely, the relationship S1>E1 may also satisfy.
[0210] Fig.30 Schematically showing that a Fig.29 An example of the shape of multiple recesses in a composite film in which the lead wires of the recesses are connected is shown. Fig.30 In the example shown, each recess 228 extends in a direction inclined relative to one side of the tab region, for example.
[0211] exist Fig.30 In the example shown, Fig. 22 In contrast to the example shown, the width S7 in the -45° direction of the opening 28a of one of the two concave portions 228 adjacent to each other in the -45° direction and the distance E7 in the -45° direction between the openings 28a of the two concave portions satisfy the relationship S7<E7. Of course, the relationship S7>E7 may also satisfy.
[0212] Fig.31 Another example of the shape and arrangement of the recessed portion formed on the upper surface of the lead is schematically shown. Fig.24 , Fig. 27 and Fig.29 As shown in the example, when the opening 61a of the recessed portion 61 has a strip shape such as a strip, the strip shape of the opening 61a may also be Fig.31 As shown in the example, the corners are rounded. Fig. 27 Similarly, in the example shown Fig.31 In the example shown, the relationship X1>Y1 also holds. In addition, if the distance D4 between the openings 28a of two adjacent concave portions 228 in the Y direction in the figure is compared with the width Y1 of the opening 61a of the concave portion 61 in the Y direction, the relationship D4>Y1 holds. Conversely, the relationship D4<Y1 may also hold.
[0213] Fig.32 Schematically showing that a Fig.31 An example of the shape of the plurality of recesses of the composite film in which the lead wires of the recesses are connected. Fig.32 As schematically shown, similar to the shape of the opening 61a of the recess 61 formed on the upper surface of the lead, the elongated shape of the opening 28a of the recess 228 formed in the composite film may be a shape with rounded corners. Fig.28 In the example shown, the relationship of X7>Y7 and the relationship of D10>Y7 are established here as well. The relationship of D10<Y7 may also be established.
[0214] The width of the strip shape of the opening 61 a and / or the width of the strip shape of the opening 28 a may be constant or variable along the extending direction of the strip shape. Fig.33 Another example of the shape and arrangement of the recessed portion formed on the upper surface of the lead is schematically shown. Fig.33 In the illustrated structure, the plurality of recessed portions 61 include recessed portions 61U and recessed portions 61V arranged along the Y direction in the figure.
[0215] like Fig.33As shown schematically, the opening 61a of the recess 61U has a shape in which the width in the Y direction increases as it advances along the X direction in the figure. That is, the width of the opening 61a of the recess 61U in the Y direction in the figure is different at each position in the X direction in the figure. For example, the width Y2 of the left end of the opening 61a of the recess 61U is smaller than the width Y3 of the right end. On the other hand, Fig.33 In the example shown, the opening 61 a of the recess 61V has a shape in which the width in the Y direction decreases as it goes along the X direction in the figure.
[0216] In this example, the distance D5 between the opening 61a of the recess 61U and the opening 61a of the recess 61V in the Y direction in the figure is constant regardless of the position in the X direction in the figure. Of course, the shape of the opening 61a of the recess 61U and the shape of the opening 61a of the recess 61V may be such that the distance D5 changes depending on the position in the X direction in the figure. In addition, in this example, the width of the opening 61a of the recess 61U and the width of the opening 61a of the recess 61V in the X direction in the figure are both X1 and are equal.
[0217] Fig.34 Schematically showing that a Fig.33 An example of the shape of multiple recesses in a composite film in which the lead wires of the recesses are connected is shown. Fig.34 In the illustrated example, the plurality of recesses 228 formed in the laminate of the composite film 225A include recesses 228U and recesses 228V arranged along the Y direction in the figure.
[0218] exist Fig.34 In the illustrated structure, the opening 28a of the recess 228U has a shape in which the width in the Y direction increases as it advances along the X direction in the figure. On the other hand, the opening 28a of the recess 228V has a shape in which the width in the Y direction decreases as it advances along the X direction in the figure. Here, the width Y8 of the left end portion of the opening 28a of the recess 228U is smaller than the width Y9 of the right end portion. The distance D11 between the opening 28a of the recess 228U and the opening 28a of the recess 228V in the Y direction in the figure may be constant regardless of the position in the X direction in the figure, or may be different at each position in the X direction in the figure.
[0219] When viewed from the stacking direction of the composite film 225A, the recessed portion 61 and / or the recessed portion 228 may have a curved shape. Fig.35 Another example of the shape and arrangement of the recessed portion formed on the upper surface of the lead is schematically shown. Fig.35In the illustrated structure, the opening 61a of the recess 61 has a shape that meanders in the XY plane of the figure, and includes a curved portion 61d in a part thereof. In this example, the width Y1 of the opening 61a of the recess 61 in the Y direction and the distance D4 between the openings 61a of two recesses 61 adjacent to each other in the Y direction in the figure satisfy the relationship D4>Y1. The relationship D4<Y1 may also satisfy. In addition, in this example, the width X1 of the opening 61a of the recess 61 in the X direction is greater than the width Y1 in the Y direction.
[0220] Fig.36 Schematically showing that a Fig.35 An example of the shape of multiple recesses in a composite film in which the lead wires of the recesses are connected is shown. Fig.36 In the illustrated structure, the opening 28a of the recessed portion 228 has a curved portion 28d in a portion thereof, and has a shape that meanders in the XY plane of the figure. Fig.36 In the example shown, the width Y7 of the opening 28a of the concave portion 228 in the Y direction and the distance D10 between the openings 28a of two concave portions 228 adjacent to each other in the Y direction in the figure satisfy the relationship D10>Y7. The relationship D10<Y7 may also satisfy. In addition, in this example, the width X7 of the opening 28a of the concave portion 228 in the X direction is greater than the width Y7 in the Y direction.
[0221] Fig.37 Another example of the shape and arrangement of the recessed portion formed on the upper surface of the lead is schematically shown. Fig.35 Similarly, in the example Fig.37 In the illustrated structure, the opening 61a of the recess 61 has a shape that meanders in the XY plane of the figure, and includes a curved portion 61d in part thereof. However, in this example, the width Y1 of the opening 61a of the recess 61 in the Y direction is greater than the width X1 in the X direction. That is, here, Y1>X1.
[0222] exist Fig.37 In the example shown, the width X1 of the opening 61a of the recess 61 in the X direction and the distance D1 between the openings 61a of two adjacent recesses 61 in the X direction in the figure satisfy the relationship D1>X1. The relationship D1<X1 may also satisfy.
[0223] Fig.38 Schematically showing that a Fig.37 An example of the shape of multiple recesses in a composite film in which the lead wires of the recesses are connected is shown. Fig.38 In the illustrated structure, the opening 28a of the recess 228 has a curved portion 28d in a portion thereof, and has a shape that meanders in the XY plane of the figure. Fig.38In the example shown, the meandering shape of the opening 28a of each recess 228 extends longer in the Y direction than in the X direction in the figure. That is, here, the relationship Y7>X7 is established between the width Y7 of the opening 28a of the recess 228 in the Y direction and the width X7 in the X direction.
[0224] exist Fig.38 In the example shown, the width X7 of the opening 28a of the recess 228 in the X direction and the distance D7 between the openings 28a of two adjacent recesses 228 in the X direction in the figure satisfy the relationship D7>X7. The relationship D7<X7 may also satisfy.
[0225] Thus, the shape of the opening 61a of the recess 61 on the upper surface 260a of the lead 260 is not limited to a dotted shape or a straight line shape, but may be a curved shape, or a shape formed by combining a straight line and a curved line, etc. The shape of the opening 28a of the recess 228 formed in the laminate of the composite film 225A is also not limited to a dotted shape or a straight line shape. The shape of the opening 28a of the recess 228 may be a curved shape, or a shape formed by combining a straight line and a curved line, etc. For example, by forming the bonding portion 25 into a meandering shape, the bonding interface between the lead and the composite film can be enlarged, and the bonding strength between them can be further improved.
[0226] Fig.39 Another example of the connection between the second electrode and the lead wire in the single cell is schematically shown. Fig.39 In, with Figure 7 Similarly, among the composite films 225A included in the unit cell 200A, two sheets of composite film 225Ak located at the bottom layer of the stacked structure of the first electrode 210A and the second electrode 220A and composite film 225Ah located at the upper layer are extracted and shown.
[0227] exist Fig.39 In the illustrated structure, the composite film 225A is connected to the second region R2 of the upper surface 260a of the lead 260. Here, the upper surface 260a of the lead 260 including the first region R1 and the second region R2 is a flat surface as a whole. In this way, the upper surface 260a of the lead 260 connected to the laminated body of the tab region 210t of the composite film 225A may also be a flat surface. In other words, the upper surface 260a of the lead 260 connected to the laminated body of the tab region 210t may not have the above-mentioned recessed portion 61.
[0228] like Fig.39As shown in an enlarged manner in FIG. 2 , in this example, the third portion 240J includes a plurality of bonding portions 25. These bonding portions 25 are respectively arranged at positions overlapping with the second region R2 of the upper surface 260a of the lead 260 when viewed in the Z direction in the figure. As described later, the bonding portion 25 is a portion where solid phase bonding occurs between the first conductive layer 21 and the second conductive layer 22 of the composite film 225A. In addition, solid phase bonding is also formed between the bonding portion 25 and the lead 260. In addition, for example, as shown in FIG. Fig.16 As in the described example, when the composite film 225A and the lead 260 are connected at the positions of the lattice points of the rectangular lattice, the first region R1 can be formed in a lattice shape on the upper surface 260 a of the lead 260 .
[0229] The bonding portion 25 may have a smaller thickness than other portions of the composite film 225A (e.g., a portion overlapping the second material layer 222 in the stacking direction). On the other hand, for a portion of the composite film 225A located between two second regions R2 adjacent to each other on the upper surface 260a of the lead 260, as shown in FIG. Fig.39 As shown schematically, it may be in a shape that bulges in a direction away from the lead 260. Focus on the distance in the Z direction in the figure from the upper surface 22a of the second conductive layer 22 of, for example, the composite film 225Ak in the laminate of the composite film 225A to the lead 260. Here, the distance from the position farthest from the lead 260 in the portion of the upper surface 22a of the second conductive layer 22 overlapping with the first region R1 in the Z direction in the figure to the lead 260 is greater than the thickness of the portion overlapping with the second region R2 in the Z direction in the figure. In this example, it can also be said that: in the laminate of the composite film 225A, a plurality of recesses 228 are formed at positions corresponding to the second region R2 of the upper surface 260a of the lead 260 in the Z direction in the figure.
[0230] Thus, the portion of the upper surface 260a of the lead 260 connected to the composite film 225A may not have the recess 61. The second region R2 having the recess 61 in a portion thereof and the second region R2 not having the recess 61 may exist in the upper surface 260a of the lead 260 in a mixed manner. Of course, the same method as described above may also be applied between the first electrode 210A and the lead 250 in the single cell 200A. Fig.39 The connection structure shown is the same as the joint structure.
[0231] (Variant 1)
[0232] Fig.40 Modifications of the power storage device according to one embodiment of the present invention are shown. Fig.40 The structure shown is another example of a stacked lithium ion secondary battery. Fig.40The lithium ion secondary battery 100B shown includes a unit cell 200B including one or more groups of positive and negative electrodes, a pair of leads 250 and 260 connected to the unit cell 200B, an exterior body 300 covering the unit cell 200B, and an electrolyte 290 .
[0233] Fig.41 Will Fig.40 The single cell 200B of the power storage device shown in the figure is taken out and its structure is schematically shown. Figure 2 Similar to the cell 200A shown, the cell 200B includes: one or more first electrodes 210B, one or more second electrodes 220B, and a third layer 270B for preventing direct contact between them. The composite film 215B of each first electrode 210B has a tab region 210t formed by not disposing the first material layer 212 on its surface. Similarly, the composite film 225B of each second electrode 220B also has a tab region 220t formed by not disposing the second material layer 222 on its surface.
[0234] The tab region 210t on the first electrode 210B side is provided at a position where the first electrodes 210B overlap each other in the Z direction of the figure, and is connected to the lead 250 on the first electrode 210B side. In this example, the lead 250 is connected to the second surface 215b side of the composite film 215B of the first electrode 210B located at the bottom layer. The tab region 220t on the second electrode 220B side is also provided at a position where the second electrodes 220B overlap each other in the Z direction of the figure, and is connected to the lead 260 on the stack of the tab region 220t. In this example, the lead 260 is connected to the fourth surface 225b side of the composite film 225B of the second electrode 220B located at the bottom layer.
[0235] With reference Figure 2 Compared with the examples shown in Fig.41 In the example shown, the lead region 210t and the lead region 220t are both led out toward the same side (here, the negative side of the X direction) in the X direction in the figure in the stacked structure of the first electrode 210B and the second electrode 220B. The lead region 210t on the first electrode 210B side and the lead region 220t on the second electrode 220B side are in a direction perpendicular to the stacking direction of the first electrode 210B and the second electrode 220B, and can be either Figure 2 As shown in the example, they are located on opposite sides of each other, but they can also be Fig.41 The example shown leads in the same direction.
[0236] exist Fig.41In the example shown, the third layer 270B is a single thin sheet. The third layer 270B has a shape bent into a Z-shape in the single cell 200B. The third layer 270B includes a plurality of portions respectively located between the first material layer 212 of the first electrode 210B and the second material layer 222 of the second electrode 220B. The first electrode 210B is respectively located on one surface side of the third layer 270B, and the second electrode 220B is respectively located on the other surface side of the third layer 270B.
[0237] In this way, the separator can be arranged in a single cell in the form of a single sheet. Figure 2 As in the example shown in FIG. 1 , the separator may include a plurality of sheets respectively located between the positive electrode and the negative electrode. In addition, when the single cell 200B is cut along a plane parallel to the ZX plane in the figure, the same structure as in FIG. 1 can be obtained except for the arrangement of the lead region. Figure 7 or Fig.39 The cross sections shown are substantially the same cross sections. Therefore, illustration of the cross section of the cell 200B is omitted here.
[0238] (Variant 2)
[0239] Fig.42 Another modified example of the power storage device according to one embodiment of the present invention is shown. Fig.42 Another example of a stacked lithium ion secondary battery as an electricity storage device is shown. Fig.42 The lithium ion secondary battery 100C shown includes: a unit cell 200C including a group of positive and negative electrodes; a pair of leads 250 and 260 connected to the unit cell 200C; an exterior body 300 covering the unit cell 200C; and an electrolyte 290 .
[0240] Fig.42 The cell 200C shown has a first electrode 210C, a second electrode 220C, and two third layers 270Ca and 270Cb. The cell 200C has a so-called wound structure in which the first electrode 210C, the third layer 270Ca, the second electrode 220C, and the third layer 270Cb are stacked in sequence and then the stacked body is wound. Fig.42 In the example shown, the cell 200C has a flat shape as a whole, but the present invention is not limited to this example, and the cell 200C may also have a cylindrical shape or the like.
[0241] In the above examples (for example, see Fig.41 ), each positive electrode is provided with a single lead region 210t, and in contrast, Fig.42 In the illustrated structure, the first electrode 210C has four lead regions 210t. Fig.42In the illustrated structure, the second electrode 220C also has four lead regions 210t. The lead regions 210t on the first electrode 210C side are stacked in the Z direction in the figure and connected to the lead 250. Similarly, the lead regions 220t on the second electrode 220C side are stacked in the Z direction in the figure and connected to the lead 260. Fig.42 As shown, the third portion 240J is formed on the tab region 210t and the tab region 220t.
[0242] Fig.43 express Fig.42 The stacked structure of the first electrode, the second electrode, and the separator in the single cell is shown. Fig.43 The first electrode 210C, the third layer 270Ca, the second electrode 220C, and the third layer 270Cb are schematically shown in a state before winding. The third layers 270Ca and 270Cb are thin sheets having a rectangular shape that is longer in the Y direction than in the X direction in the figure. The first electrode 210C and the second electrode 220C each have a rectangular shape that extends in the Y direction in the figure except for the lead region. By overlapping and winding these sheet-like components, a structure in which the first electrode 210C and the second electrode 220C are alternately stacked in the Z direction in the figure with the third layer 270Ca or 270Cb interposed therebetween is achieved.
[0243] Fig.44 It indicates that Fig.42 The second electrode 220C of the cell 200C includes a second material layer 222 and a composite film 225C supporting the second material layer 222. In this example, the second material layer 222 is disposed on both surfaces of the sheet-like composite film 225C.
[0244] The basic structure of the composite film 225C is the same as that of the composite films 225A and 225B described above, except that a plurality of the lead-tab regions 220t are provided instead of the single lead-tab region 220t. Fig.44 As shown in an enlarged manner in FIG. 2 , the composite film 225C includes: a first conductive layer 21 ; a second conductive layer 22 ; and a first layer 24 located between the first conductive layer 21 and the second conductive layer 22 .
[0245] Fig.45 It indicates that Fig.42 The first electrode is taken out of the single cell shown in FIG. Fig.45As shown in FIG. 1 , the first electrode 210C includes a first material layer 212 and a composite film 215C supporting the first material layer 212. The basic structure of the composite film 215C is the same as that of the composite films 215A and 215B described above, except that a plurality of tab regions 210t are provided instead of a single tab region 210t. As in the above-described examples, the composite film 215C includes a first conductive layer 11, a second conductive layer 12, and a first layer 14 located between the first conductive layer 11 and the second conductive layer 12.
[0246] The first material layer 212 on the first electrode 210C side is formed in a strip shape on the composite film 215C and is not provided on the tab region 210t. Similarly, the second material layer 222 on the second electrode 220C side is formed in a strip shape on the composite film 225C and is not provided on the tab region 220t.
[0247] Refer again Fig.43 The composite film 215C of the first electrode 210C has a plurality of lead regions 210t extending from one side of the rectangular shape to the negative side of the X direction in the figure. These lead regions 210t are arranged in the composite film 215C so as to overlap in the Z direction in the figure when the first electrode 210C, the third layer 270Ca, the second electrode 220C, and the third layer 270Cb are stacked and rolled. Therefore, when the first electrode 210C is made flat, the lead regions 210t may not be arranged at equal intervals in the Y direction in the figure. That is, it may also be: Fig.43 The distance between two adjacent lead regions 210t indicated by double arrows L1 and L2 holds the relationship L1≠L2.
[0248] The composite film 225C of the second electrode 220C also has a plurality of lead regions 220t respectively extending from one side of the rectangular shape toward the negative side in the X direction in the figure. These lead regions 220t are also arranged at irregular intervals in the Y direction in the figure when the first electrode 210C, the third layer 270Ca, the second electrode 220C, and the third layer 270Cb are stacked and rolled up so as to overlap in the Z direction in the figure, and typically, in a state where the second electrode 220C is flat.
[0249] Thus, instead of providing a single lead-in area for each electrode (positive electrode or negative electrode), multiple lead-in areas may be provided on the composite film of a single electrode. By configuring lead-in areas at multiple locations of a single electrode, the current can be dispersed to each lead-in area during the charge and discharge of the storage device. That is, it is possible to avoid the current being concentrated in a single lead-in area during charge and discharge, and to suppress the local excessive temperature rise caused by the concentration of current. Thus, the structure of providing multiple lead-in areas is conducive to improving the reliability of the storage device. The number and configuration of the lead-in areas in the composite film can be appropriately changed according to the size of the storage device, the number of windings of the electrode, etc.
[0250] (Variant 3)
[0251] Fig.46 Another modification of the power storage device according to one embodiment of the present invention is shown. Fig.42 The lithium-ion secondary battery 100C shown in the figure is also Fig.46 Compared with the lithium-ion secondary battery 100C, Fig.46 The lithium ion battery 100D shown has a single cell 200D instead of the single cell 200C. Compared with the single cell 200C of the lithium ion secondary battery 100C, the single cell 200D includes a group of a first electrode 210D and a second electrode 220D instead of the group of the first electrode 210C and the second electrode 220C. The single cell 200D is arranged in the internal space of the outer casing 300 together with the electrolyte 290 in a state where a pair of leads 250 and 260 are connected.
[0252] Fig.47 Schematically Fig.46 The first electrode, the second electrode and the separator in the single cell are shown in FIG. Fig.47 As shown, the first electrode 210D includes a first material layer 212 and a composite film 215D supporting the first material layer 212. A lead region 210t is provided on the composite film 215D. The basic structure of the composite film 215D is similar to that of the reference 1 except that the number of lead regions 210t is different. Fig.45 The composite film 215D is the same as the composite film 215C described above. That is, the composite film 215D includes the first conductive layer 11 , the second conductive layer 12 , and the first layer 14 located between the first conductive layer 11 and the second conductive layer 12 .
[0253] The second electrode 220D includes a second material layer 222 and a composite film 225D supporting the second material layer 222. The basic structure of the composite film 225D is similar to that of the reference numeral 220D, except that the number of tab regions 220t is one. Fig.44The composite film 225D is the same as the composite film 225C described above. That is, the composite film 225D includes the first conductive layer 21 , the second conductive layer 22 , and the first layer 24 located between the first conductive layer 21 and the second conductive layer 22 .
[0254] The first electrode 210D, the third layer 270Ca, the second electrode 220D, and the third layer 270Cb are sequentially stacked and then rolled up to obtain a laminated body. Fig.46 The shape of the cell 200D is not limited to a flat shape, and may be a cylindrical shape or the like.
[0255] Below, with Figure 2 The components of the power storage device according to the first embodiment of the present invention will be described in more detail by taking the lithium ion secondary battery 100A shown as an example.
[0256] (Composite membrane 215A, 225A)
[0257] As reference Figure 3 and Figure 4 As described, in the embodiment of the present invention, composite films 215A and 225A supporting active material layers are composite materials in which conductive layers are provided on both surfaces of a supporting layer containing a resin, etc. The composite film 215A has the first conductive layer 11 on one surface of the first layer 14 and the second conductive layer 12 on the other surface, thereby playing the role of a collector of the first electrode 210A. The composite film 225A has the first conductive layer 21 on one surface of the first layer 24 and the second conductive layer 22 on the other surface, thereby playing the role of a collector of the second electrode 220A.
[0258] Examples of the first layer 14 of the composite film 215A and the first layer 24 of the composite film 225A are sheets with thermoplastic resin as the base material. As the base materials of the first layer 14 and the first layer 24, polyester resins, polyamide resins, polyethylene resins, polypropylene resins, polyolefin resins, polystyrene resins, polyurethane resins, acetal resins, cellophane and ethylene-vinyl alcohol copolymer (EVOH), polyimide and polyvinyl chloride can be used. Examples of polyolefin resins include polyethylene (PE) and polypropylene (PP). Polyolefin resins can also be acid-modified polyolefin resins. Examples of polyester resins include polybutylene terephthalate (PBT) and polyethylene naphthalate. Examples of polyamide resins include nylon 6, nylon 66 and poly(m-xylene adipamide) (MXD6). Examples of polystyrene resins include polystyrene (PS). For example, a uniaxially stretched sheet or a biaxially stretched sheet of polyethylene terephthalate or a biaxially stretched sheet of polypropylene can be suitably used for the first layer 14 and / or the first layer 24 .
[0259] The same material as that of the diaphragm can also be applied to the base material of the first layer 14 and the first layer 24. The material of the first layer 14 of the composite film 215A and the material of the first layer 24 of the composite film 225A can be the same or different from each other. The first layer 14 and / or the first layer 24 can be provided in the form of a laminated film containing two or more of the above materials. The first layer 14 and / or the first layer 24 can further contain a fireproofing agent, etc.
[0260] In consideration of the improvement of energy density and the strength as a current collector, the first layer 14 and the first layer 24 are formed to have a thickness in the range of, for example, 3 μm or more and 12 μm or less. The first layer 14 and the first layer 24 preferably have a thickness in the range of 3 μm or more and 6 μm or less. In addition, the first layer 14 and the first layer 24 are not limited to the form of a resin film, and one or both of the first layer 14 and the first layer 24 may also be provided in the form of a nonwoven fabric or a porous film containing a thermoplastic resin. One or both of the first layer 14 and the first layer 24 may have a single-layer structure or a multi-layer laminated structure.
[0261] The composite film 215A on the first electrode 210A side includes the first conductive layer 11 and the second conductive layer 12 supported by the first layer 14. Figure 3 As described above, when applied to the positive electrode of a lithium ion secondary battery, a typical example of the first conductive layer 11 and the second conductive layer 12 is a conductive film containing aluminum (aluminum film or aluminum alloy film). As the material of the first conductive layer 11 and / or the second conductive layer 12, titanium, chromium, stainless steel or nickel, or an alloy containing one or more of them can also be applied.
[0262] The first conductive layer 11 and the second conductive layer 12 can be formed by a known semiconductor process. For example, evaporation, sputtering, electrolytic plating, electroless plating, etc. can be used. After a seed layer of nickel chromium or the like is formed on the surface of the first layer 14 by sputtering, an aluminum film is formed on the seed layer by electrolytic plating, electroless plating, evaporation, etc., thereby obtaining the first conductive layer 11 and the second conductive layer 12. The thickness of each of the first conductive layer 11 and the second conductive layer 12 can be in the range of 50 nm to 5 μm, preferably in the range of 100 nm to 2 μm (for example, about 0.5 μm). The first conductive layer 11 and the second conductive layer 12 are not limited to single-layer films. One or both of the first conductive layer 11 and the second conductive layer 12 may include multiple layers. A protective layer for inhibiting oxidation may also be further formed on the surface of the first conductive layer 11 and the second conductive layer 12.
[0263] In addition, Figure 3The diagram shows a mode in which the first conductive layer 11 and the second conductive layer 12 are in direct contact with the first layer 14 respectively, but other functional layers may be present between the first conductive layer 11 and the first layer 14 and / or between the second conductive layer 12 and the first layer 14. For example, a primer layer may be disposed between the first conductive layer 11 and the first layer 14 and between the second conductive layer 12 and the first layer 14. The primer layer may be a layer formed of an organic material such as an acrylic resin or a polyolefin resin, or a layer containing a metal formed by sputtering. By providing the primer layer, the conductive layer (the first conductive layer 11 and the second conductive layer 12) may be more firmly bonded to the first layer 14 and / or the formation of pinholes in the conductive layer may be suppressed.
[0264] Similar to the composite film 215A, the composite film 225A on the second electrode 220A side includes the first conductive layer 21 and the second conductive layer 22 supported by the first layer 24. Figure 4 As described above, when applied to the negative electrode of a lithium ion secondary battery, typical examples of the first conductive layer 21 and the second conductive layer 22 are conductive films containing copper (copper films or films of copper alloys).
[0265] The first conductive layer 21 and the second conductive layer 22 can be formed by a known semiconductor process. For example, after a seed layer of nickel chromium (NiCr) is formed on the surface of the first layer 24 by sputtering, a copper film is formed on the seed layer by electrolytic plating, thereby obtaining the first conductive layer 21 and the second conductive layer 22. The first conductive layer 21 and the second conductive layer 22 are not limited to the form of a single layer film. Similar to the first conductive layer 11 and the second conductive layer 12 on the first electrode 210A side, the thickness of each of the first conductive layer 21 and the second conductive layer 22 can also be in the range of 50 nm or more and 5 μm or less, preferably in the range of 100 nm or more and 2 μm or less (for example, about 0.5 μm).
[0266] Similar to the composite film 215A on the first electrode 210A side, a primer layer or the like may be interposed between the first conductive layer 21 and the first layer 24 and between the second conductive layer 22 and the first layer 24. The first conductive layer 21 and the second conductive layer 22 may each have a protective layer or the like on the surface thereof.
[0267] (First material layer 212)
[0268] When applied to the positive electrode of a lithium ion secondary battery, the first material layer 212 of the first electrode 210A contains at least a material capable of absorbing and releasing lithium ions as a positive electrode active material. The first material layer 212 may further contain a binder, a conductive additive, etc. A base coat containing carbon may also be sandwiched between the composite film 215A and the first material layer 212.
[0269] An example of a material capable of absorbing and releasing lithium ions is a composite metal oxide containing lithium. Examples of such composite metal oxides include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), lithium manganese spinel (LiMn2O4), lithium vanadium compound (LiV2O5), olivine-type LiMPO4 (wherein M is one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, Zr, or vanadium oxide), lithium titanate (Li4Ti5O 12 ), with the general formula LiNi x Co y Mn z MaO2 (x+y+z+a=1, 0≤x<1, 0≤y<1, 0≤z<1, 0≤a<1, M in the above general formula is one or more elements selected from Al, Mg, Nb, Ti, Cu, Zn, Cr) represented by a composite metal oxide, and a general formula LiNi x Co y Al z A composite metal oxide represented by O2 (0.9<x+y+z<1.1), etc. The first material layer 212 may contain polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene, etc. as a material capable of absorbing and releasing lithium ions.
[0270] Various known materials can be used as the binder in the first material layer 212. As the binder in the first material layer 212, fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), ethylene-tetrafluoroethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), and polyvinyl fluoride (PVF) can be used.
[0271] As the adhesive in the first material layer 212, a vinylidene fluoride-based fluororubber may also be used. For example, a vinylidene fluoride-hexafluoropropylene-based fluororubber (VDF-HFP-based fluororubber), a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene-based fluororubber (VDF-HFP-TFE-based fluororubber), a vinylidene fluoride-pentafluoropropylene-based fluororubber (VDF-PFP-based fluororubber), a vinylidene fluoride-pentafluoropropylene-tetrafluoroethylene-based fluororubber (VDF-PFP-TFE-based fluororubber), a vinylidene fluoride-perfluoromethyl vinyl ether-tetrafluoroethylene-based fluororubber (VDF-PFMVE-TFE-based fluororubber), a vinylidene fluoride-chlorotrifluoroethylene-based fluororubber (VDF-CTFE-based fluororubber), etc. may also be used as the adhesive in the first material layer 212.
[0272] Examples of the conductive additive in the first material layer 212 include carbon materials such as carbon powder and carbon nanotubes. Carbon black or the like can be used as the carbon powder. Other examples of the conductive additive in the first material layer 212 include metal powders such as nickel, stainless steel, and iron, and powders of conductive oxides such as ITO. Two or more of the above materials may be mixed and the first material layer 212 may contain them.
[0273] (Second material layer 222)
[0274] When applied to the negative electrode of a lithium-ion secondary battery, the second material layer 222 of the second electrode 220A contains at least a material capable of absorbing and releasing lithium ions as a negative electrode active material. Similar to the first material layer 212 on the first electrode 210A side, the second material layer 222 may further contain a binder, a conductive additive, etc. A primer layer containing carbon may also be sandwiched between the composite film 225A and the second material layer 222.
[0275] When applied to lithium-ion secondary batteries, examples of materials that can be applied to the second material layer 222 include natural or artificial graphite, carbon nanotubes, difficult-graphitizable carbon, easily-graphitizable carbon (soft carbon), low-temperature fired carbon and other carbon materials. Other examples of materials that can be applied to the second material layer 222 include alkali metals and alkaline earth metals such as metallic lithium, and metals such as tin or silicon that can form compounds with metals such as lithium. Silicon-carbon composite materials can also be applied to the second material layer 222. The second material layer 222 can also contain an amorphous compound (SiO x (0<x<2), tin dioxide, etc.), lithium titanate (Li4Ti5O 12 ) and other particles.
[0276] The materials exemplified as the binder and the conductive aid that can be applied to the first material layer 212 on the first electrode 210A side can be applied to the binder and the conductive aid of the second material layer 222. In addition to the above-mentioned materials, cellulose, styrene-butadiene rubber, ethylene-propylene rubber, polyimide resin, polyamide-imide resin, acrylic resin, etc. can be used as the binder in the second material layer 222 on the second electrode 220A side.
[0277] (Lead wires 250, 260)
[0278] The lead wire 250 and the lead wire 260 are plate-shaped members formed of a conductive material. Examples of the material of the lead wire 250 on the first electrode 210A side include aluminum and aluminum alloys. Typical examples of the material of the lead wire 260 on the second electrode 220A side include nickel and nickel alloys. The lead wire 260 may also have a copper-plated layer on its surface.
[0279] The lead wires 250 and 260 in the above-mentioned examples are respectively rectangular conductive plates. Of course, the shapes of the lead wires 250 and 260 are not limited to rectangular plates. Various shapes such as a shape bent into an L-shape when viewed perpendicularly to the XY plane, a shape having a through hole, a shape bent in the Z direction, etc. may be adopted.
[0280] (3rd floor 270A)
[0281] The third layer 270A is an insulating component that prevents electrical short circuit between the first electrode 210A and the second electrode 220A and allows lithium ions to pass through by being arranged between the first material layer 212 and the second material layer 222 closest to the first material layer 212 in the single cell 200A. The third layer 270A may also have a ceramic coating on its surface. The thickness of the ceramic coating is, for example, in the range of 2 μm or more and 5 μm or less. The third layer 270A as a whole has a thickness in the range of 5 μm or more and 30 μm or less, for example. The thickness of the third layer 270A is more preferably in the range of 8 μm or more and 20 μm or less.
[0282] When an electrolyte is applied to the electrolyte 290, an insulating porous material is used for the third layer 270A. Typical examples of such porous materials include: a single-layer film or a laminated film of polyolefins such as polyethylene and polypropylene; or a non-woven fabric of at least one fiber selected from cellulose, polyester, polyacrylonitrile, polyimide, polyamide (e.g., aromatic polyamide), polyethylene, and polypropylene. Alternatively, the third layer 270A may also be a porous film. The electrolyte is not only arranged between the first material layer 212 and the third layer 270A on the side of the first electrode 210A, and between the second material layer 222 and the third layer 270A on the side of the second electrode 220A, but also arranged in the gaps in the third layer 270A.
[0283] (Electrolyte 290)
[0284] As electrolyte 290, for example, a non-aqueous electrolyte containing a metal salt such as a lithium salt and an organic solvent can be used. As lithium salts, for example, LiPF6, LiClO4, LiBF4, LiCF3SO3, LiCF3CF2SO3, LiC(CF3SO2)3, LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(CF3CF2CO)2, LiBOB, etc. can be used. One of these lithium salts can be used alone, or two or more can be mixed. From the viewpoint of ionization degree, it is preferred that electrolyte 290 contains LiPF6.
[0285] Regarding the solvent of the electrolyte 290, for example, an organic solvent containing a cyclic carbonate and a chain carbonate can be applied. Examples of cyclic carbonates that can be applied to the electrolyte 290 include ethylene carbonate, propylene carbonate, butylene carbonate, and the like. It is beneficial for the organic solvent to contain at least propylene carbonate as a cyclic carbonate. The addition of chain carbonates reduces the kinematic viscosity of the organic solvent. As chain carbonates, diethyl carbonate, dimethyl carbonate, or ethyl methyl carbonate can be used. The volume ratio between the cyclic carbonate and the chain carbonate in the non-aqueous solvent is preferably in the range of 1:9 to 1:1. The organic solvent may also further contain methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, and the like.
[0286] The concentration of the electrolyte in the non-aqueous electrolyte is beneficial in the range of 0.5 mol / L or more and 2.0 mol / L or less. When the concentration of the electrolyte is 0.5 mol / L or more, the lithium ion concentration of the non-aqueous electrolyte is ensured, and sufficient capacity is easily obtained during charge and discharge. When the concentration of the electrolyte is 2.0 mol / L or less, the mobility of the lithium ions of the non-aqueous electrolyte is suppressed, and sufficient capacity is easily obtained during charge and discharge.
[0287] A solid electrolyte layer may also be used as the electrolyte 290. As the material of the solid electrolyte layer, a material selected from La 0.5 Li 0.5 TiO3 and other perovskite compounds, Li 14 Zn(GeO4)4 and other LISICON type (lithium zinc germanate type) compounds, Li7La3Zr2O 12 Garnet compounds such as LiZr2(PO4)3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 1.5 Al 0.5 Ge 1.5 (PO4)3 and other NASICON compounds, Li 3.25 Ge 0.25 P 0.75 S4, Li3PS4 and other thio-LISICON compounds, Li2S-P2S5, Li2O-V2O5-SiO2 and other glass compounds, as well as Li3PO4, Li 3.5 Si 0.5 P 0.5 O4、Li 2.9 PO 3.3 N 0.46 At least one of the phosphate compounds.
[0288] (External body 300)
[0289] The outer casing 300 is a covering member that holds the single cell 200A and the electrolyte 290 therein. The outer casing 300 has a function of protecting the single cell 200A and the electrolyte 290 from external moisture, etc. In a structure in which an electrolyte solution is used for the electrolyte 290, the outer casing 300 also has a function of preventing the electrolyte solution from leaking to the outside.
[0290] The outer casing 300 is, for example, a laminated film in which a resin film is formed on both sides of a metal foil. A representative example of the metal foil used in the laminated film of the outer casing 300 is aluminum foil. As the resin coating the metal foil, for example, a polymer such as polypropylene can be applied. The material of the resin film covering the surface of the single cell 200A side of the metal foil (the inner surface of the outer casing 300) and the material of the resin film covering the surface on the opposite side to the single cell 200A may be the same material or different materials. For example, the surface of the single cell 200A side of the surface of the metal foil may be covered with polyethylene, polypropylene, etc., and the surface on the opposite side may be covered with a resin material having a higher melting point, such as polyethylene terephthalate, polyamide (PA), etc.
[0291] As the outer casing 300, in addition to the laminated film, a metal can or the like can also be used. When a metal can is used as the outer casing 300, a valve for discharging the gas generated inside is sometimes provided on the can. In addition, sometimes both the positive electrode and the negative electrode are provided with active material layers on both sides of the composite film as a current collector. In such a structure, the active material layer is located at the outermost side of the single cell 200A, and sometimes a protective component for ensuring electrical insulation is arranged between the can as the outer casing 300 and the single cell 200A. As the material of such a protective component, the same material as the third layer 270 can be applied.
[0292] The exterior body 300 may be a covering member of a resin formed by curing epoxy resin or the like. In other words, the exterior body 300 may be a resin itself formed by potting.
[0293] [Method for manufacturing power storage device]
[0294] Hereinafter, an exemplary method for manufacturing an electric storage device will be described with reference to the accompanying drawings. Figure 2 The manufacturing method will be described by taking the lithium ion secondary battery 100A of the illustrated single cell 200A as an example.
[0295] Fig.48 An outline of an exemplary method for manufacturing an electric storage device according to another embodiment of the present invention is shown. Fig.48The manufacturing method of the illustrated energy storage device roughly includes: a process of arranging a composite film and a conductor plate between an anvil and a welding head having a protrusion (step S1); a process of applying ultrasonic vibration to the welding head while pressing the area of the composite film located between the protrusion of the welding head and the anvil against the upper surface of the conductor plate (step S2); a process of moving a portion of the material of the supporting layer of the composite film toward the outside of the protrusion of the welding head so that the first conductive layer and the second conductive layer of the composite film are in contact with each other (step S3); and a process of moving a portion of at least one of the first conductive layer and the second conductive layer of the composite film toward the lower surface of the conductor plate to a position deeper than the upper surface (step S4).
[0296] First, the lead 250, the plurality of first electrodes 210A, the lead 260, and the plurality of second electrodes 220A are prepared. Each of the plurality of first electrodes 210A and each of the plurality of second electrodes 220A can be obtained, for example, by preparing a resin sheet having a conductive film on both sides of the resin layer, forming the first material layer 212 or the second material layer 222 as an active material layer on each of the upper surface and the lower surface of the resin sheet, and then cutting the resin sheet into a predetermined shape.
[0297] When forming the first material layer 212 and the second material layer 222, first, prepare a slurry containing an active substance, a binder and a solvent, and apply the slurry to the surface of the resin sheet. As a solvent, an organic solvent such as methanol, ethanol, propanol, N-methyl-2-pyrrolidone, N,N-dimethylformamide, or water can be used. When applying the slurry, a blade coater, a slit die coater, a rod coater, etc. can be used. Alternatively, when applying the slurry, screen printing or gravure printing can also be used. At this time, the slurry is not applied to the entire surface of the resin sheet, and an area to which the slurry is not applied remains. After applying the slurry to the resin sheet, the solvent in the slurry is removed by drying.
[0298] After the slurry layer is dried, the thickness of the slurry layer is adjusted by a roller pressing device or the like. The density of the active material in the first material layer 212 and the second material layer 222 can be controlled by the pressing pressure. Then, the resin sheet is cut into a predetermined shape. By cutting the resin sheet in a manner including an area not provided with slurry, an electrode (positive electrode or negative electrode) including a composite film having a lead region and an active material layer (the first material layer 212 or the second material layer 222) on the composite film can be obtained.
[0299] Here, a resin sheet having an aluminum film on both sides of a resin layer is used to form the first electrode 210A, and a slurry containing a positive electrode active material is applied to the resin sheet. On the other hand, in the formation of the second electrode 220A, a resin sheet having a copper film on both sides of a resin layer is used, and a slurry containing a negative electrode active material is applied to the resin sheet. For the lead on the first electrode 210A side, an aluminum plate having a thickness of about 150 μm can be applied; for the lead on the second electrode 220A side, a nickel plate having a thickness of about 150 μm can be applied.
[0300] Then, if Figure 2 As shown in FIG. 1 , the first electrode 210A and the second electrode 220A are alternately stacked with the third layer 270A as a separator therebetween to assemble the single cell 200A. At this time, the plurality of first electrodes 210A and the plurality of second electrodes 220A are stacked so that the tab regions 210t on the first electrode 210A side and the tab regions 220t on the second electrode 220A side overlap each other.
[0301] Then, the lead wire 250 is connected to the lead-tab region 210t of the plurality of first electrodes 210A included in the single cell 200A, and the lead wire 260 is connected to the lead-tab region 220t of the plurality of second electrodes 220A. The specific method of connecting the lead wires is basically the same between the first electrode 210A side and the second electrode 220A side. Therefore, here, the connection between the lead-tab region 220t of the plurality of second electrodes 220A and the lead wire 260 is described, and the illustration and description of the connection between the lead-tab region 210t of the plurality of first electrodes 210A and the lead wire 250 are omitted.
[0302] In this embodiment, a stack of a lead wire and a plurality of composite films is arranged between an anvil and a welding head having one or more protrusions on the surface, and the plurality of composite films are connected to the lead wire by ultrasonic bonding. Here, the connection between the lead wire and the electrode is achieved by ultrasonic bonding using transverse ultrasonic vibration.
[0303] Fig.49 1 shows an exemplary tip shape of a horn applicable to ultrasonic bonding between a lead wire and a composite film. Fig.49 The upper surface 80a of the illustrated welding head 80A has a plurality of convex portions 84A each having a quadrangular pyramidal shape. Fig.49 In the example shown, each convex portion 84A has a quadrangular pyramid shape including a rectangular top surface 84a. Examples of the material of the welding head 80A include titanium and iron.
[0304] The shape of each convex portion of the welding head is not limited to Fig.49 Shape shown. Fig.50 Other examples of the tip shape of the horn applicable to ultrasonic bonding between a lead wire and a composite film are shown. Fig.50The welding head 80B shown has a plurality of protrusions 84B on its upper surface 80a. Each of the plurality of protrusions 84B has a rod shape extending in one direction on the upper surface 80a. In this example, the top surface 84a of each protrusion 84B has a rectangular shape.
[0305] exist Fig.49 and Fig.50 In the illustrated structure, each convex portion 84A and each convex portion 84B has a trapezoidal cross-sectional shape. Fig.49 and Fig.50 The shapes of the convex portions of the welding head shown are merely examples, and the shapes of the convex portions of the welding head are of course not limited to these examples.
[0306] When connecting the plurality of lead regions 220t to the lead wire 260, first, Fig.51 As shown in FIG. 1 , the lead wire 260 and the plurality of composite films 225A are arranged between the welding head 80 and the anvil 90. In this case, a welding head 80 having a plurality of protrusions 84 is used, and the lead wire 260 and the plurality of composite films 225A are arranged between the welding head 80 and the anvil 90 in such a manner that the plurality of protrusions 84 face the lead region 220t of the composite film 225A. As the welding head 80, for example, Fig.49 The welding head 80A of the illustrated shape, or Fig.50 The welding head 80B of the illustrated shape.
[0307] like Fig.51 As shown, the lead wire 260 is supported on the upper surface 90a of the anvil 90, and a plurality of composite films 225A are located on the upper surface 260a of the lead wire 260. Fig.51 As shown, the upper surface 90a of the anvil 90 may also have a plurality of protrusions 94. The plurality of protrusions 94 are provided to suppress positional deviation of the lead 260 during the ultrasonic bonding process. In other words, by using an anvil 90 having a concave-convex shape on the surface, it is possible to reduce the deviation in alignment of the lead 260 with respect to the laminate of the composite film 225A caused by the movement of the lead 260 on the anvil 90 when ultrasonic vibration is applied. Fig.51 In the example shown, the dimensions of each protrusion 94 of anvil 90 are smaller than the dimensions of protrusion 84 of horn 80 .
[0308] Next, the convex portion 84 of the horn 80 is brought into contact with the third surface 225a of the uppermost composite film 225A to perform ultrasonic bonding. At this time, first, the horn 80 is lowered toward the anvil 90, the convex portion 84 of the horn 80 is used to press the laminated body of the composite film 225A, and then ultrasonic vibration is applied to the horn 80. By applying ultrasonic vibration to the horn 80 after pressing the laminated body of the composite film 225A with the horn 80, it is possible to suppress the positional deviation of the composite film 225A between the horn 80 and the anvil 90.
[0309] like Fig.52 As schematically shown by the thick double arrow VB, in the present embodiment, the lateral vibration in the Z direction in the figure, that is, the direction perpendicular to the stacking direction of the plurality of composite films 225A, is applied to the ultrasonic bonding. Here, a reciprocating motion along the X direction in the figure is applied to the welding head 80. The amplitude of the lateral vibration is, for example, about 10 to 50 μm. In addition, the ultrasonic vibration applied to the welding head 80 does not necessarily have to be a linear reciprocating motion. It can also be: combining the vibrations in two directions perpendicular to the stacking direction of the composite film 225A, and applying the composite vibration to the welding head 80. For example, ultrasonic bonding can also be performed by applying an elliptical vibration in a plane perpendicular to the stacking direction of the composite film 225A to the welding head 80.
[0310] Here, the convex portion 84 of the welding head 80 has a trapezoidal shape including a top surface 84a in the cross-sectional view. Therefore, as the welding head 80 descends, the top surface 84a of the convex portion 84 first contacts the third surface 225a of the uppermost composite film 225A. In the ultrasonic bonding process, the composite film 225A on the anvil 90 is pressed by the welding head 80, and ultrasonic vibration is applied to the welding head 80, thereby, the region of the composite film 225A sandwiched by the convex portion 84 of the welding head 80 and the anvil 90 is pressed against the anvil 90, and is compressed in the stacking direction.
[0311] At this time, due to the ultrasonic vibration, part of the resin material in the first layer 24 of the composite film 225A melts, and the composite film 225A is compressed from top to bottom. In addition, part of the resin material moves between the first conductive layer 21 and the second conductive layer 22 to the outside of the protrusion 84 of the welding head 80. As a result, in the area between the protrusions 84 of the welding head 80, the first layer 24 is compressed from left to right, as shown in FIG. Fig.52 As schematically shown, composite membrane 225A is deformed. Fig.52 In the illustrated example, a portion of the composite film 225A located between two convex portions 84 of the welding head 80 is deformed so as to bulge toward the bottom of a valley 84 v formed between the convex portions 84 .
[0312] That is, by applying ultrasonic vibration to the welding head 80 while pressing the composite film 225A with the protrusion 84 of the welding head 80, the resin in the first layer 24 can be squeezed out to the outside of the protrusion 84 of the welding head 80 by lateral vibration and pressure. In particular, in the case where the welding head 80 has a plurality of protrusions 84, the molten resin moves between the first conductive layer 21 and the second conductive layer 22. As a result, the portion of the composite film 225A sandwiched between two adjacent protrusions 84 of the welding head 80 is subjected to pressure from the left and right, and a portion with increased thickness is generated in the first layer 24. That is, by using a welding head 80 having a plurality of protrusions 84 to perform the joining between the lead 260 and the composite film 225A, a portion whose thickness has changed compared to before the joining process can be generated in the first layer 24. For example, by allowing the resin material to flow from the left and right into the portion of the first layer 24 located between the two protrusions 84 during the ultrasonic joining process, a region whose thickness has increased compared to before the ultrasonic joining is performed can be formed. In other words, by using a welding head 80 having a plurality of protrusions 84, the reference Figure 8 The first portion 24X described above is formed in the first layer 24 of the composite film 225A.
[0313] On the other hand, the thickness of the first layer 24 of the composite film 225A overlapping with the second material layer 222 when viewed in the Z direction in the figure (ie, the stacking direction of the composite film 225A) does not change before and after the bonding step. Figure 7 The second portion 24Y shown is a portion of the first layer 24 that is located outside the region sandwiched between the horn 80 and the anvil 90 in the joining process.
[0314] In the composite film 225A and the lead 260, the focus is on the region sandwiched between the anvil 90 and the top surface 84a of the convex portion 84 of the welding head 80. Unlike the resin material in the first layer 24, the first conductive layer 21 and the second conductive layer 22 of the composite film 225A do not melt even when subjected to ultrasonic vibration. Due to the compression between the anvil 90 and the convex portion 84 of the welding head 80, in the region of the first layer 24 of the composite film 225A sandwiched between the convex portion 84 of the welding head 80 and the anvil 90, a portion of the resin material in the first layer 24 is squeezed outward from the convex portion 84, and in contrast, tensile stress is generated in the first conductive layer 21 and the second conductive layer 22 toward these regions.
[0315] Fig.53 One of the protrusions 84 of the welding head 80 and its surroundings are shown in an enlarged manner. Fig.53 In FIG. 1 , among the plurality of composite films 225A on the lead 260, one of the bottom layers closest to the lead 260 and one layer located above the bottom layer are taken out and schematically shown. Fig.53In the illustrated example, the laminated body of the composite film 225A is pressed against the lead 260 supported by the anvil 90 by the projection 84 of the horn 80 , so that the recess 61 is formed on the upper surface 260 a of the lead 260 . Fig.53 Parts of the two composite films 225A are shown located within the recess 61 .
[0316] As described above, by applying ultrasonic vibration and pressure, a portion of the material of the region sandwiched between the protrusion 84 of the welding head 80 and the anvil 90 in the first layer 24 of the composite film 225A moves to the outside of the region. A portion of the material constituting the first layer 24 is squeezed outward from the region sandwiched between the protrusion 84 of the welding head 80 and the anvil 90, thereby causing at least a portion of the first conductive layer 21 spatially separated by the first layer 24 to contact the second conductive layer 22. Further, solid phase bonding occurs between the first conductive layer 21 and the second conductive layer 22, and a conductive path is formed between the first conductive layer 21 and the second conductive layer 22. That is, by applying ultrasonic vibration and pressure, the first conductive layer 21 and the second conductive layer 22 are electrically connected to each other in the region sandwiched between the protrusion 84 of the welding head 80 and the anvil 90.
[0317] Solid phase bonding also occurs between one first conductive layer 21 and the other second conductive layer 22 of two adjacent composite films 225A. That is, a conductive path is also formed between the first conductive layer 21 and the second conductive layer 22 facing each other between the two composite films 225A, and as a result, a plurality of composite films 225A can be electrically connected. In addition, by applying ultrasonic vibration and pressure, solid phase bonding also occurs between the first conductive layer 21 of the composite film 225A at the bottom and the lead 260, and a conductive path is formed therebetween. That is, a conductive path can be formed afterwards between the first conductive layer 21 and the second conductive layer 22 in the composite film 225A of each second electrode 220A, and the first conductive layer 21 and the second conductive layer 22 in the composite film 225A of the plurality of second electrodes 220A included in the single cell 200A can be electrically connected to the lead 260 at once.
[0318] In this way, by utilizing ultrasonic bonding, the lead 260 can be mechanically and electrically connected to the lead area 220t of the second electrode 220A in the single cell 200A. In this sense, the term "bonding" used in this specification basically refers to a "welding" method. By ultrasonic bonding, a conductive path is formed not only between the composite film 225A of the second electrode 220A located at the bottom layer of the single cell 200A and the lead 260, but also between the composite films 225A of the second electrodes 220A adjacent to each other. Furthermore, by applying ultrasonic bonding, a conductive path can also be formed between the first conductive layer 21 and the second conductive layer 22 in the composite film 225A of each second electrode 220A.
[0319] Generally speaking, in ultrasonic bonding of resin parts, so-called longitudinal vibration is applied to the horn (also called "sonotrode") in parallel with the direction of pressure applied by the horn. In contrast, in the present embodiment, ultrasonic vibration (lateral vibration) is applied perpendicular to the direction of pressure applied by the horn. The application of such lateral vibration makes it easy to extrude the resin in the region between the convex portion of the horn and the anvil in the support layer of the composite film to the outside. In other words, it is easier to form a conductive path between two conductive layers in the composite film separated by the support layer containing an insulating material than in the case of applying longitudinal vibration.
[0320] By applying pressure and ultrasonic vibration, the resin material in the first layer 24 is squeezed outward from the area between the protrusion 84 of the welding head 80 and the anvil 90 in the first layer 24 of the composite film 225A, and solid phase bonding occurs between the lead 260 and the conductive layers (the first conductive layer 21 and the second conductive layer 22) on both sides of each composite film 225A. By strongly pressing the composite film against the anvil 90 using the protrusion 84, a recess 61 corresponding to the protrusion 84 of the welding head 80 can be formed on the surface of the lead opposite to the composite film. That is, according to an embodiment of the present invention, even in the case of using a composite film having conductive layers separated by an insulating material such as a resin, for example, at a position overlapping with the recess of the lead in the stacking direction of the composite film, a conductive path can be formed between these conductive layers and between these conductive layers and the lead.
[0321] The preferred conditions for ultrasonic bonding can vary depending on the material of the lead, the material and thickness of the conductive layer in the composite film, the thickness of the laminate of the composite film, the shape of the welding head, the arrangement pitch, etc. Regarding the conditions for ultrasonic bonding in the case of applying lateral vibration, for example, the following ranges can be set. In addition, the following ranges are only examples and do not limit the conditions for ultrasonic bonding of this embodiment. In addition, the amplitude is expressed as a ratio relative to the device output (e.g., 800W).
[0322] Pressing pressure: 0.05MPa~0.5MPa
[0323] Amplitude: 50%~100%
[0324] Vibration time: 0.2s~1.0s
[0325] Oscillation frequency: 10kHz~40kHz (e.g. 20kHz or 40kHz)
[0326] In the laminate of the composite film 225A, the portion overlapping with the recess 61 when viewed in the Z direction in the figure excludes most of the resin in the first layer 24 of each composite film 225A during the ultrasonic bonding process, thereby reducing the thickness of the laminate as a whole. Furthermore, the joint 25 is formed by solid-phase bonding between the material of the first conductive layer 21 and the material of the second conductive layer 22 of the plurality of composite films 225A. By compression between the protrusion 84 of the welding head 80 and the anvil 90, the thickness of the joint 25 produced on the composite film 225A can be reduced compared to other portions of the composite film 225A (for example, the portion overlapping with the second material layer 222 in the stacking direction). In addition, by excluding most of the resin in the first layer 24 of each composite film 225A during the ultrasonic bonding process, the thickness of the laminate as a whole is reduced, as shown in reference. Fig.39 As in the example described above, the same also applies when no recess is formed on the upper surface of the lead.
[0327] like Fig.53 As shown schematically, most of the bonding portion 25 can be located inside the recess 61 of the lead 260 when viewed along the Z direction in the figure. Fig. 9 As described above, a part of the resin material in the first layer 24 may remain in the region of the first layer 24 sandwiched between the protrusion 84 of the horn 80 and the anvil 90 .
[0328] exist Fig.53 In the example shown, the resin 24r derived from the resin material of the first layer 24 of the composite film 225A of the lowest layer and the resin 24r derived from the resin material of the first layer 24 of the composite film 225A of one layer above are located inside the bonding portion 25. In this example, these resins 24r are located deeper than the portion located in the first region R1 of the upper surface 260a of the lead 260, and a portion of the third surface 225a of the composite film 225A is also located deeper than the upper surface 260a. This means that the first conductive layer 21 and the second conductive layer 22 of the composite film 225A are moved to the lower surface 260b to a position deeper than the upper surface 260a of the lead 260 by the pressure of the horn 80 during ultrasonic bonding.
[0329] like Fig.55 When the bonding portion 25 is formed by including the resin 24r as in the example shown in the figure, the bonding time and / or bonding conditions can be relaxed compared to the case where the bonding portion does not include the resin, so it is advantageous in terms of manufacturing cost. In addition, in the process of forming the bonding portion 25, excessive stress can be prevented from being applied to the composite film 225A, so the reduction in the conductivity of the composite film 225A can be suppressed.
[0330] As described above, solid phase bonding occurs between the material of the first conductive layer 21 of the composite film 225A and the material of the lead 260. From the perspective of whether a bonding interface is formed between the material of the first conductive layer 21 of the composite film 225A and the material of the lead 260, the position of the boundary between the first region R1 and the second region R2 of the upper surface 260a of the lead 260 can be determined. When the second region R2 is observed in the Z direction in the figure, the bonding interface between the material of the first conductive layer 21 of the composite film 225A and the material of the lead 260 may extend to the outside of the recess 61 included in the second region R2. That is, in the top view, the range of the second region R2 may not coincide with the range of the recess 61 located in the second region R2.
[0331] The shapes of the recesses 61 on the lead 260 and the configuration of the recesses 61 can be adjusted according to the shapes of the protrusions 84 of the welding head 80 and the configuration of the protrusions 84. For example, by applying Fig.49 The welding head 80A having a plurality of convex portions 84A each in the shape of a quadrangular pyramid on the upper surface 80a as shown in FIG. Fig.16 Configuration as shown or Fig.17 The arrangement shown forms the recess 61 on the lead 260. The size relationship between the width X1 of the opening 61a of the recess 61 and the distance D1 between the openings 61a can be changed by, for example, adjusting the arrangement of the protrusions 84A of the welding head 80A and / or the shape of each protrusion 84A.
[0332] In addition, when the welding head 80A having the convex portion 84A in the shape of a quadrangular pyramid is used, a concave portion in the shape of an inverted quadrangular pyramid defined by four inner wall surfaces corresponding to the shape of the convex portion 84A can be formed on the laminate of the composite film 225A. For example, by adjusting the arrangement of the convex portion 84A and / or the shape of each convex portion 84A, the size relationship between the width X7 of the opening 28a of the concave portion 228 and the distance D5 between the openings 28a can be changed.
[0333] Even when a common welding head 80A is used, the shape of the recessed portion 228 may be changed depending on the number of sheets of the composite film 225A connected to the lead 260. When the number of sheets of the composite film 225A connected to the lead 260 is large, it is beneficial to arrange the protrusions 84A arranged on the upper surface 80a of the welding head 80A relatively sparsely. This is because it is easy to ensure space in the valley portion between the protrusions 84A to accommodate the composite film 225A that is deformed due to compression between the protrusions 84A of the welding head 80A and the anvil 90. When the number of sheets of the composite film 225A connected to the lead 260 is large, such as Fig.19 The arrangement of the recessed portion 228 in which the relationship X7<D5 is established as illustrated is advantageous.
[0334] The arrangement of the protrusions 84 on the upper surface 80a of the welding head 80 is not limited to Fig.49 The projections 84 may be arranged at unequal intervals on the upper surface 80a of the welding head 80, or the projections 84 may not be provided in a part of the upper surface 80a. By arranging the projections 84 at unequal intervals on the upper surface 80a of the welding head 80, or by mixing the projections 84 of different shapes, it is possible to use a single welding head 80 to connect a variety of composite films. For example, by arranging the projections 84 at unequal intervals, it is possible to achieve the connection of a plurality of composite films. Fig.18 The arrangement of the recessed portions 228 described above, that is, the distances D5, D6, and D7 between the openings 28a in different groups each including two recessed portions 228, can achieve D5≠D6 or D5≠D7. Alternatively, it can achieve the following: Fig.16 The arrangement of the recessed portions 61 described above, that is, the distances D1 , D2 , and D3 between the openings 61 a in different groups each including two recessed portions 61 , can achieve D1 ≠ D2 or D1 ≠ D3 .
[0335] replace Fig.49 The welding head 80A shown in FIG. Fig.50 The welding head 80B shown in the figure, which is provided with a convex portion 84B having a rectangular top surface 84a, is used for ultrasonic bonding, thereby forming a Fig.24 , Fig. 27 , Fig.29 or Fig.31 The recess 61 of the shape shown. In this way, according to the embodiment of the present invention, the configuration and shape of the recess formed on the upper surface of the lead and / or the configuration and shape of the recess formed in the laminate of the composite film can be adjusted according to the shape of the front end of the welding head. The shape of each convex portion 84 of the welding head 80 is not limited to a quadrangular pyramid or a quadrangular column, and may also be a conical shape. The height of each convex portion and the center-to-center distance between two adjacent convex portions can be appropriately changed according to the number of composite films connected to the lead, etc.
[0336] As described above, according to the present embodiment, by applying ultrasonic bonding using a combination of a welding head 80 and anvil 90 having a shape that matches the structure of a composite film 225A including the first conductive layer 21 and the second conductive layer 22 that are spatially separated from each other by the first layer 24, most of the resin located between the first conductive layer 21 and the second conductive layer 22 can be excluded from a part of the composite film 225A. At this time, the first conductive layer 21 and the second conductive layer 22 in the composite film 225A are pulled toward the recess 61, while on the other hand, the portion located between the two recesses 61 of the lead 260 in the first layer 24 is compressed from the left and right. As a result, as Figure 8 As shown in the example, a portion with increased thickness can be formed in the portion of the first layer 24 located between the two recessed portions 61 in the cross-sectional view. Fig.39 As shown in the example, a portion with increased thickness can be formed in a portion of the first layer 24 located between the two second regions in the cross-sectional view. Instead of this, or in addition to this, the composite film 225A can be deformed between the protrusions 84 of the welding head 80 so that the overall thickness of the laminate of the composite film 225A is increased compared to before ultrasonic bonding at a position overlapping with the first region R1 of the lead 260 in the Z direction of the figure.
[0337] At the position between two adjacent concave portions 61 (or the second region R2), one of the plurality of composite films 225A disposed on the lead 260, in particular, the one located on the top layer, is compressed from left and right between the convex portions 84 of the welding head 80, and is thus easily deformed into a shape corresponding to the shape of the surface of the convex portions 84 of the welding head 80 (which may also be referred to as the shape of the valley formed between the convex portions 84). In other words, the cross-sectional shape of the composite film 225A after ultrasonic bonding is mostly a gentle curved shape.
[0338] On the other hand, when a composite film 225A located near the lead 260 among the plurality of composite films 225A is compressed from the left and right, there is often no space sufficient to accommodate its deformation between the composite film 225A on the upper layer and the lead 260. Fig. 9 and Fig.10 In other words, by using the welding head 80 provided with a plurality of convex portions 84, during the ultrasonic bonding process, a portion of the composite film 225A located between the two concave portions 61 (or the second region R2) of the lead 260 can be entangled. Figure 11 to Figure 14 The example shown is an entangled shape.
[0339] By bending the conductive layer of the composite film or the composite film itself between the two recesses (or the second region R2) of the lead, the same effect as when a plurality of conductive layers are stacked in a direction perpendicular to the first region of the upper surface of the lead, or the same effect as when the substantial thickness of the insulating layer is locally increased, can be obtained, and cracking of the composite film 225A under shear stress can be suppressed. Compared with simply applying heat and pressure to the composite film, by using ultrasonic vibration, it is easy to form a composite film such as Figure 11 to Figure 14 The conductive layer of the composite film or the composite film itself in the example shown is entangled in a portion located between the two recessed portions (or the second region R2) of the lead in the cross-sectional view.
[0340] Through the above-mentioned steps, the third portion 240J (for example, see Figure 5 ). Alternatively, the third portion 240J may be formed at a plurality of locations in the tab region 220t by changing the location in contact with the horn 80 and repeatedly performing ultrasonic bonding.
[0341] According to an embodiment of the present invention, the proportion of the area where the lead and the composite film are joined in the third portion 240J can also be adjusted according to the shape of the front end of the welding head. For example, by increasing the area ratio of the second region R2 as a whole relative to the first region R1, the effect of reducing the connection resistance between the lead and the conductive layer of the composite film can be obtained. However, if the area of the top surface of each convex portion of the welding head is simply increased, as the area of the top surface is increased, it may be difficult to move the resin in the support layer from the area of the composite film support layer sandwiched by the convex portion of the welding head and the anvil to the outside.
[0342] However, by adjusting the number and arrangement of the convex portions of the welding head, the expansion of the area of the top surface of each convex portion can be avoided, and the area ratio of the second region R2 as a whole relative to the first region R1 can be increased. For example, by sparsely arranging the convex portions of the welding head or increasing the intervals between the convex portions, the space between the convex portions can be expanded. That is, it is possible to ensure space between the convex portions of the welding head that can accommodate the deformation of the composite film. In addition, if the area of the top surface of each convex portion is simply reduced, the connection resistance of each portion where the joint 25 is formed will increase, but the increase in connection resistance can be avoided by increasing the number of convex portions of the welding head. In addition, by increasing the number of convex portions of the welding head, it is also possible to obtain an effect of avoiding local concentration of current when using a storage device.
[0343] The surface of the anvil supporting the lead wire may be a flat surface or a surface having projections and depressions. For example, by using an anvil having projections and depressions on the surface, one or more recesses may be provided on the lower surface 260b side of the lead wire 260. Fig.51 and Fig.52 As shown, here, an anvil 90 having a plurality of protrusions 94 provided on an upper surface 90a is used. When such an anvil 90 is used, the composite film 225A and the lead wire 260 are pressed against the anvil 90 by the welding head 80, thereby Fig. 9 and Fig.10 As shown, a plurality of recesses ( Fig. 9 recess 62A and Fig.10 recess 62B).
[0344] Fig.54 An example of the appearance of the lower surface of the lead after ultrasonic bonding is performed is shown. Fig.54In the example shown, a plurality of recesses 62 are formed on the lower surface 260b of the lead 260. These recesses 62 are formed at positions corresponding to the protrusions 94 of the anvil 90. The shape and arrangement of the recesses on the lower surface side of the lead can be variously changed according to the shape of the surface of the anvil.
[0345] In the technology described in Patent Document 1, a lead and a current collector are sandwiched between an anvil having a convex portion on the surface and a welding head having a flat surface, and ultrasonic vibration is applied to the welding head to perform bonding between these components. Here, as the current collector, a film having a metal film formed on both sides of a resin layer is used. As a result of ultrasonic bonding, a concave portion is formed on the surface of the lead on the anvil side, and the surface of the lead on the opposite side is sunken into the inside of the film (Patent Document 1). Fig.25 ). In the technology described in Patent Document 1, the surface of the lead on the film side is made to protrude into the film, so that the metal films on the film upper surface side and the film lower surface side are brought into contact with each other.
[0346] However, since the connection between the metal films of the film is achieved by the deformation of the lead, the contact between the metal films may require a higher pressure. In particular, depending on the choice of the material of the lead, it is sometimes difficult to make the surface of the lead protrude into the inside of the film, and the film may be damaged during ultrasonic bonding. For example, when applied to lithium-ion secondary batteries, a combination of a resin film with a copper film on both sides and a lead formed by nickel can be applied. In this case, since nickel is hard, high pressure is required for the deformation of the lead, and particularly when a relatively large convex portion is provided on the surface of the anvil, the film may be damaged at the position of the contact point with these convex portions.
[0347] In contrast, in the present embodiment, a plurality of protrusions are provided on the welding head side to which ultrasonic vibration is applied, so that these protrusions are opposite to the composite film. Therefore, it is possible to effectively apply ultrasonic vibration to the composite film while avoiding excessive pressure. According to the present embodiment, the composite film can be connected to the lead without damaging the function of the composite film as a current collector. In addition, since a plurality of protrusions are provided on the welding head side, the portion of the composite film that is deformed due to pressure can be accommodated in the valley portion between the protrusions. Therefore, the portion of the composite film sandwiched between the protrusions of the welding head bulges toward the opposite side of the lead compared to before ultrasonic bonding is performed, and in these portions, it is possible to achieve the connection as described in reference to FIG. Figures 9 to 14 Thus, for example, a mechanically entangled structure can be introduced between the overlapping composite films, and the composite film can be prevented from being damaged or falling off from the lead due to external force.
[0348] After the ultrasonic bonding process is performed, the single cell 200A connected to the leads 250 and 260 is housed in the outer casing 300, and the electrolyte 290 is arranged in the inner space of the outer casing 300. Then, the outer periphery of the outer casing 300 is sealed in such a way that a part of each of the leads 250 and 260 is located outside the outer casing 300. Figure 1 The secondary battery 100A is shown.
[0349] [Embodiment 2 of Power Storage Device]
[0350] Fig.55 An example of the structure of an electric storage device according to still another embodiment of the present invention is shown. Fig.55 The structure of an electric double layer capacitor as an electricity storage device is shown.
[0351] Fig.55 The electric double layer capacitor 100E shown has: a single cell 200E including one or more groups of positive and negative electrodes; a pair of leads 250 and 260 connected to the single cell 200E; an outer casing 300 covering the single cell 200E; and an electrolyte 290E. In this example, the single cell 200E has a pair of first electrodes 210E and second electrodes 220E. As described later, the first electrode 210E and the second electrode 220E respectively include a composite film 215 and a composite film 225 having conductive layers on both sides. A lead region 210t is provided on the composite film 215, and a lead 250 is connected to the lead region 210t via a third portion 240J. Similarly, a lead region 220t is provided on the composite film 225, and a lead 260 is connected to the lead region 220t via a third portion 240J.
[0352] Fig.56 Schematically Fig.55 A cross section of an electric double layer capacitor 100E is shown. Fig.56 This corresponds to a cross-sectional view when the electric double layer capacitor 100E is cut parallel to a plane including the stacking direction (Z direction in the figure) of the first electrode 210E and the second electrode 220E in the unit cell 200E.
[0353] like Fig.56 As schematically shown, the single cell 200E of the electric double layer capacitor 100E is sealed together with the electrolyte 290E in the internal space of the outer casing 300. In this example, the outer casing 300 has a first resin film 301 and a second resin film 302, and a metal foil 304 sandwiched between these resin films. A portion of the lead 250 and a portion of the lead 260 are located outside the outer casing 300, and function as a positive electrode terminal and a negative electrode terminal, respectively.
[0354] exist Fig.56In the illustrated structure, the single cell 200E includes a pair of the first electrode 210E and the second electrode 220E, and a third layer 270E disposed between the first electrode 210E and the second electrode 220E. The first electrode 210E has a first material layer 212E disposed on the composite film 215, and the second electrode 220E has a second material layer 222E disposed on the composite film 225. In addition, in the application of the double-layer capacitor of the embodiment of the present invention, it is not necessary to make the materials of the conductive layer different between the composite film 215 on the first electrode 210E side and the composite film 225 on the second electrode 220E side. The composite film 215 may be applied to both the collector of the first electrode 210E and the collector of the second electrode 220E, or the composite film 225 may be applied to both the collector of the first electrode 210E and the collector of the second electrode 220E.
[0355] In this example, the first material layer 212E of the first electrode 210E is formed on a portion of the first surface 215a of the composite film 215, and the second material layer 222E of the second electrode 220E is formed on a portion of the fourth surface 225b of the composite film 225. The third layer 270E is located between the first material layer 212E of the first electrode 210E and the second material layer 222E of the second electrode 220E. When applied to an electric double layer capacitor, the material constituting the first material layer 212E of the first electrode 210E and the second material layer 222E of the second electrode 220E may be the same.
[0356] like Fig.56 As shown schematically, the upper surface 250a of the lead 250 on the first electrode 210E side has a plurality of recesses 51, and the composite film 215 of the first electrode 210E is connected to the lead 250 at the positions of these recesses 51. In addition, the first conductive layer 11 and the second conductive layer 12 of the composite film 215 are connected to each other at the positions of the recesses 51. Fig.56 In the example shown, by referring to Figure 7 and Figure 8 The same structure as the example of connecting the composite film 225A to the lead 260 described above realizes electrical connection from the first material layer 212 of the first electrode 210E to the lead 250 via the composite film 215 .
[0357] Although not shown in the figure, a connection similar to the reference connection is also formed between the composite film 225 on the second electrode 220E side and the lead 260. Figure 7 and Figure 8 That is, the first conductive layer 21 and the second conductive layer 22 in the composite film 225 on the second electrode 220E side are also electrically connected to the lead 260 at the positions of the plurality of recesses 61 on the upper surface 260 a of the lead 260 .
[0358] In addition, the upper surface 250a of the lead 250 does not necessarily have the recess 51. Fig.39 The same connection structure as in the example described above can be realized between the composite film 215 and the lead 250 of the first electrode 210E. Similarly, the composite film 225 and the lead 260 on the second electrode 220E side can also be connected to each other. Fig.39 The example illustrates the same connection structure.
[0359] The electrical connection and mechanical connection between the composite film of the collector and the lead can be formed, for example, by ultrasonic bonding. By forming a conductive path by ultrasonic bonding, it is possible to suppress the lead from falling off the composite film, and it is also possible to suppress the composite film from being damaged starting from the periphery of the third part between the lead and the composite film, thereby providing a double-layer capacitor with excellent reliability.
[0360] Hereinafter, components of the electric double layer capacitor 100E will be described in more detail.
[0361] (First material layer 212E, second material layer 222E)
[0362] As described above, the first material layer 212E on the first electrode 210E side and the second material layer 222E on the second electrode 220E side can be formed of a common material. A representative example of the active material in the first material layer 212E and the second material layer 222E is activated carbon. As the active material of the first material layer 212E and the second material layer 222E, in addition to the graphite and carbon nanotubes exemplified as the material of the second material layer 222 for the lithium ion secondary battery, carbon materials such as fullerene and graphene can also be used.
[0363] As the active material of the first material layer 212E and the second material layer 222E, a silicon-containing carbon material can also be used. The silicon-containing carbon material can be obtained according to the method described in Japanese Patent Gazette No. 2020-064971. The silicon-containing carbon material is obtained by, for example, mixing tetramethoxysilane, tetraethoxysilane, tetrabutoxysilane, etc. with carbon materials such as activated carbon in ethanol as a solvent, and further adding water and hydrochloric acid and drying it. For reference, the entire disclosure of Japanese Patent Gazette No. 2020-064971 is cited in this specification.
[0364] As a binder for the first material layer 212E and the second material layer 222E, for example, a conductive polymer such as polyacetylene can be used. The conductive polymer also functions as a conductive auxiliary agent.
[0365] (Electrolyte 290E)
[0366] As the electrolyte 290E, an aqueous electrolyte, a non-aqueous electrolyte or an ionic liquid can be used. The solute of the non-aqueous electrolyte is a salt containing cations and anions. As the cation, a quaternary ammonium such as tetraethylammonium, triethylmethylammonium, spiro-(1,1')-bipyrrolidinium or diethylmethyl-2-methoxyethylammonium (DEME) can be used, or an imidazolium such as 1,3-dialkylimidazolium, 1,2,3-trialkylimidazolium, 1-ethyl-3-methylimidazolium (EMI) or 1,2-dimethyl-3-propylimidazolium (DMPI) can be used. As the anion, BF4 can be used. - PF6 - 、ClO4 - 、AlCl4 - or CF3SO3 - .
[0367] As the solvent of the non-aqueous electrolyte, acetonitrile, propionitrile, dimethylformamide, tetrahydrofuran, dimethoxymethane, sulfolane, dimethyl sulfoxide, ethylene glycol, propylene glycol, methyl cellosolve, etc. can be used in addition to the organic solvents exemplified as the solvent of the electrolyte 290. The above organic solvents can be used alone or in combination of two or more in any ratio.
[0368] [Other Modifications]
[0369] In each of the above-mentioned embodiments, a composite film having a conductive layer on both sides is applied to the current collector on the positive electrode side and the current collector on the negative electrode side. However, it is not necessary for the embodiments of the present invention to apply such a composite film to both the positive electrode and the negative electrode. For example, a composite film may be applied to the current collector on the positive electrode side, and copper foil may be applied to the current collector on the negative electrode side. Alternatively, a composite film may be applied to the current collector on the negative electrode side, and an aluminum foil may be applied to the current collector on the positive electrode side.
[0370] (Example)
[0371] [Evaluation of Thickness Change of Laminated Structure of Current Collector]
[0372] A laminated secondary battery cell with a composite film applied to either the positive electrode collector or the negative electrode collector was assembled, and a sample was prepared in which a lead was connected to the lead region of the collector by ultrasonic bonding. In addition, a plurality of samples were prepared by changing the number of collectors and the shape of the welding head tip, and the change in thickness of the laminated structure of the collectors before and after ultrasonic bonding and the bonding properties were evaluated.
[0373] (Battery 1-1)
[0374] A single cell of battery 1-1 was produced by the following process. First, as a current collector on the positive electrode side, a composite film having an aluminum conductive layer formed on both sides of a polyethylene terephthalate sheet was prepared. Next, an active material layer was formed on the composite film while leaving a portion of the composite film. The active material layer was formed by applying a coating containing a positive electrode active material on the composite film, drying it, and then rolling it. As the positive electrode active material, lithium cobalt oxide (LiCoO2) was used. The active material layer was formed on both sides of the composite film. Next, the composite film was punched into a specified shape in such a way that the composite film contained an area where the active material layer was not provided, thereby obtaining a plurality of positive electrodes, each of which contained a composite film as a current collector and had a lead area on a portion thereof.
[0375] A plurality of negative electrodes are prepared by the same process as the positive electrode. However, here, as the collector on the negative electrode side, a copper foil without an insulating layer containing a resin is used. Furthermore, an active material layer is arranged on both sides of the copper foil. The active material layer is formed by applying a coating containing a negative electrode active material on a composite film, drying it, and then rolling it. Graphite is used as the negative electrode material.
[0376] Next, 9 positive electrodes and 10 negative electrodes were alternately stacked with a separator sandwiched therebetween to assemble a single cell. As the separator, a polyethylene separator with a thickness of 12 μm was used. At this time, the positive electrode, the negative electrode, and the separator were stacked in such a way that the negative electrode was located on the outermost side. In addition, the configuration of each electrode in the single cell was adjusted in such a way that the lead areas of the composite film of the positive electrode overlapped with each other, and the lead areas of the copper foil of the negative electrode overlapped with each other.
[0377] Next, an aluminum plate with a thickness of 100 μm was prepared as a lead on the positive electrode side, and the laminate in the lead area on the positive electrode side and the lead on the positive electrode side were connected by ultrasonic bonding. Fig.57 Ultrasonic welding is performed using a horn 80X having a plurality of protrusions 84X on the upper surface. Hardened iron is selected as the material of the horn 80X.
[0378] Fig.57The convex parts 84X of the welding head 80X shown have shapes obtained by cutting the tops of quadrangular pyramids at 90 degrees from two mutually opposite side surfaces. Each convex part 84X has a top surface 84a. In the welding head 80X, these multiple convex parts 84X are arranged on the upper surface of the welding head 80X along two directions orthogonal to each other. The arrangement pitch of the convex parts 84X, that is, the distance P1 between the centers of two adjacent convex parts 84X is 1mm. The width T1 of the top surface 84a in the cross-sectional view when the welding head 80X is cut along the arrangement direction of the multiple convex parts 84X is 0.47mm, and the width V1 of the bottom of the valley 84v formed between the two convex parts 84X is 0.05mm. The distance M1 from the bottom of the valley 84v to the top surface 84a of the convex part 84X is 0.24mm.
[0379] The conditions for ultrasonic bonding applied to the connection of the lead wire on the positive electrode side are as follows. In the following description, the "amplitude" is expressed as a ratio to the output (800 W) of the device.
[0380] Pressing pressure: 0.2MPa
[0381] Amplitude: 100%
[0382] Time of applying vibration: 0.4s
[0383] Vibration direction: lateral vibration (reciprocating motion)
[0384] Oscillation frequency: 40kHz
[0385] Number of engagements: 1
[0386] Fig.58 This is a schematic diagram showing, as a line graph, a microscope image of the third portion on the positive electrode side of the battery 1 - 1 observed in the lamination direction of the composite films. Fig.59 and Fig.60 This is a schematic diagram showing, as a line graph, a microscope image of a cross section of the third portion on the positive electrode side after ultrasonic bonding. Fig.59 The shown position is based on the LXI-LXI line cut Fig.58 Microscope images of vertical cross sections of the composite films shown. Fig.60 Equivalent to Fig.59 A partial enlarged view of Fig.59 and Fig.60 As shown, a concave portion is formed in the upper surface of the lead wire at a portion compressed in the stacking direction (Z direction in the figure) of the lead region between the convex portion 84X of the welding head 80X and the anvil. Fig.60 From the figure shown, it can be confirmed that a flat region with a width of about 450 μm is formed at the bottom of the recess 218 .
[0387] Focusing on the lead area of the current collector, it can be seen that in the portion of the upper surface of the lead that overlaps with the recessed portion, most of the resin material is driven out from between the aluminum conductive layers, forming a joint portion based on the solid-phase bonding of the conductive layers in each composite film and the solid-phase bonding between the conductive layers of two adjacent composite films. In addition, it can be confirmed that the lead and the conductive layer of the composite film are solid-phase bonded. In other words, it can be seen that electrical connection is generated between the conductive layer of each of the nine composite films and the lead.
[0388] The total thickness of the lead on the positive electrode side before ultrasonic bonding and the thickness of the laminate in the lead area is 0.16 mm. In contrast, at the position of the recessed portion of the lead, the distance from the lower surface of the lead to the upper surface of the joint is reduced to 0.11 mm after ultrasonic bonding. Among them, the distance from the lower surface of the lead to the upper surface of the joint is measured when the lead is placed on the platform. It is speculated that in the area between the convex portion 84X of the welding head 80X and the anvil in each composite film, the polyethylene terephthalate in the thin sheet supporting the conductive layer melts due to the friction heat generated by the ultrasonic vibration and moves to the area overlapping with the valley 84v of the welding head 80X.
[0389] Focus on the area between the recesses of the lead in the composite film. Fig.59 and Fig.60 As shown in FIG. 1 , between the concave portions of the lead, the composite film is compressed from left to right by the pressing of the convex portion 84X of the welding head 80X against the anvil, resulting in the composite film bulging in the direction away from the upper surface of the lead. The distance from the lower surface of the lead to the highest position of the composite film between the concave portions of the lead is 0.26 mm. That is, it can be confirmed that it has increased by 63% compared to before ultrasonic bonding. In addition, as Fig.59 and Fig.60 As shown, it can be seen that as a result of being compressed from left to right between the recessed portions of the lead wires, a shape in which the composite film is entangled is generated, especially at a position close to the lead wires.
[0390] Furthermore, the laminated body in the tab region on the negative electrode side was also connected to the lead on the negative electrode side by ultrasonic bonding. As the lead on the negative electrode side, a nickel plate with a thickness of 100 μm was used.
[0391] The conditions for ultrasonic bonding applied to the connection of the lead on the negative electrode side are as follows.
[0392] Pressing pressure: 0.1MPa
[0393] Amplitude: 50%
[0394] Time of applying vibration: 0.06s
[0395] Vibration direction: lateral vibration (reciprocating motion)
[0396] Oscillation frequency: 40kHz
[0397] Number of engagements: 1
[0398] The total thickness of the lead on the negative electrode side before ultrasonic bonding and the thickness of the laminate in the lead area was 0.18 mm. On the other hand, the distance from the lower surface of the lead to the upper surface of the uppermost composite film after ultrasonic bonding was maintained at 0.18 mm regardless of the area where solid-phase bonding occurred between the conductive layer of the composite film and the lead or the area where solid-phase bonding did not occur.
[0399] In the third part of the negative electrode, the copper foil as the current collector and the lead made of nickel are joined to each other. Solid phase bonding occurs between these components by ultrasonic bonding, but the current collector or the lead is not melted by the application of ultrasonic vibration. It can be said that the thickness of the stack of the lead and the copper foil does not change significantly before and after the ultrasonic bonding process.
[0400] After ultrasonic bonding, the single cell was covered with a laminate film as an outer casing, and an electrolyte was injected, followed by sealing the laminate film. Through the above operations, a battery 1-1 was obtained.
[0401] (Battery 1-2)
[0402] The single cell of battery 1-2 was assembled in the same manner as the single cell of battery 1-1 except that the number of positive electrodes was set to 19 and the number of negative electrodes was set to 20. Then, the laminate of the composite film on the positive electrode side was connected to the aluminum lead, and the laminate of the copper foil on the negative electrode side was connected to the nickel lead by ultrasonic bonding. However, here, a lead having a thickness of 0.2 mm was bonded to the collector on both the positive electrode side and the negative electrode side.
[0403] The conditions for ultrasonic bonding applied to the connection of the lead on the positive electrode side are as follows.
[0404] Pressing pressure: 0.25MPa
[0405] Amplitude: 100%
[0406] Vibration time: 0.5s
[0407] Vibration direction: lateral vibration (reciprocating motion)
[0408] Oscillation frequency: 40kHz
[0409] Number of engagements: 1
[0410] The conditions for ultrasonic bonding applied to the connection of the lead on the negative electrode side are as follows.
[0411] Pressing pressure: 0.125MPa
[0412] Amplitude: 50%
[0413] Time of applying vibration: 0.08s
[0414] Vibration direction: lateral vibration (reciprocating motion)
[0415] Oscillation frequency: 40kHz
[0416] Number of engagements: 1
[0417] The total thickness of the lead on the positive electrode side before ultrasonic bonding and the thickness of the laminate in the lead area was 0.32 mm. After ultrasonic bonding, the distance from the lower surface of the lead to the highest position of the composite film between the recessed parts of the lead increased to 0.68 mm. On the other hand, when focusing on the negative electrode, the distance from the lower surface of the lead to the upper surface of the uppermost copper foil was maintained at 0.32 mm before and after the ultrasonic bonding process, and no change was observed.
[0418] Then, in the same manner as battery 1-1, the single cell connected with the lead wire is placed inside the outer casing together with the electrolyte, and the outer casing is sealed to obtain battery 1-2. The thickness of the polyethylene terephthalate sheet in the composite film of each positive electrode of battery 1-1 and battery 1-2 is in the range of 5 to 7 μm, and the thickness of the aluminum conductive layer is in the range of 0.5 to 1 μm. In addition, the thickness of the copper foil of each negative electrode is in the range of 6 to 8 μm.
[0419] (Battery 1-3)
[0420] Battery 1-3 was produced by the following process. Battery 1-3 differs from Battery 1-1 in that an aluminum foil was used for the current collector on the positive electrode side instead of the composite film having a conductive layer, and a composite film was used instead of a copper foil.
[0421] First, a plurality of positive electrodes are prepared by the following process. Here, an aluminum foil without a resin insulating layer is used as a current collector on the positive electrode side. Active material layers are formed on both sides of the aluminum foil as a current collector. At this time, a portion of the upper surface and the lower surface of the foil are left, and the active material layer is arranged on the foil. Then, the foil is punched into a predetermined shape in a manner including the area on the foil where the active material layer is not provided, and a plurality of positive electrodes each including a lead area are obtained.
[0422] As a current collector on the negative electrode side, a composite film having a copper conductive layer formed on both sides of a polyethylene terephthalate sheet is prepared. Next, a portion of the composite film is left, and an active material layer is formed on both sides of the composite film. The active material layer is formed on both surfaces of the composite film. Next, the composite film is punched into a predetermined shape in a manner including an area on the composite film where the active material layer is not provided, to obtain a plurality of negative electrodes, each of which includes the composite film as a current collector and has a lead region on a portion thereof.
[0423] Next, similarly to Battery 1-1, 9 positive electrodes and 10 negative electrodes were alternately stacked with separators interposed therebetween to assemble a single cell. Then, similarly to Battery 1-1, the stacked body in the tab region on the positive electrode side was connected to the lead wire (aluminum plate with a thickness of 0.1 mm) on the positive electrode side, and the stacked body in the tab region on the negative electrode side was connected to the lead wire (nickel plate with a thickness of 0.1 mm) on the negative electrode side by ultrasonic bonding.
[0424] The conditions for ultrasonic bonding applied to the connection of the lead on the positive electrode side are as follows.
[0425] Pressing pressure: 0.1MPa
[0426] Amplitude: 45%
[0427] Time of applying vibration: 0.06s
[0428] Vibration direction: lateral vibration (reciprocating motion)
[0429] Oscillation frequency: 40kHz
[0430] Number of engagements: 1
[0431] The conditions for ultrasonic bonding applied to the connection of the lead on the negative electrode side are as follows.
[0432] Pressing pressure: 0.2MPa
[0433] Amplitude: 100%
[0434] Time of applying vibration: 0.35s
[0435] Vibration direction: lateral vibration (reciprocating motion)
[0436] Oscillation frequency: 40kHz
[0437] Number of engagements: 1
[0438] The total thickness of the lead on the positive electrode side and the thickness of the laminate in the tab region before ultrasonic bonding was 0.21 mm. After ultrasonic bonding, the distance from the lower surface of the lead to the upper surface of the uppermost aluminum foil remained unchanged at 0.21 mm, with no change observed.
[0439] The total thickness of the lead on the negative electrode side before ultrasonic bonding and the thickness of the laminate in the lead area was 0.16 mm. After ultrasonic bonding, the distance from the lower surface of the lead to the highest position of the composite film between the recessed parts of the lead increased to 0.29 mm. Then, in the same manner as battery 1-1, the single cell with the lead connected was arranged inside the outer body together with the electrolyte, and the outer body was sealed to obtain battery 1-3.
[0440] (Battery 1-4)
[0441] The single cell of battery 1-4 was assembled in the same manner as the single cell of battery 1-3 except that the number of positive electrodes was set to 19 and the number of negative electrodes was set to 20. Then, the laminate of aluminum foil on the positive electrode side was connected to an aluminum lead, and the laminate of composite film on the negative electrode side was connected to a nickel lead by ultrasonic bonding. However, here, as in battery 1-2, a lead having a thickness of 0.2 mm was bonded to the collector on both the positive electrode side and the negative electrode side.
[0442] The conditions for ultrasonic bonding applied to the connection of the lead on the positive electrode side are as follows.
[0443] Pressing pressure: 0.125MPa
[0444] Amplitude: 45%
[0445] Time of applying vibration: 0.08s
[0446] Vibration direction: lateral vibration (reciprocating motion)
[0447] Oscillation frequency: 40kHz
[0448] Number of engagements: 1
[0449] The conditions for ultrasonic bonding applied to the connection of the lead on the negative electrode side are as follows.
[0450] Pressing pressure: 0.25MPa
[0451] Amplitude: 100%
[0452] Time of applying vibration: 0.4s
[0453] Vibration direction: lateral vibration (reciprocating motion)
[0454] Oscillation frequency: 40kHz
[0455] Number of engagements: 1
[0456] Before and after the ultrasonic bonding process, the distance from the lower surface of the lead to the upper surface of the uppermost aluminum foil on the positive electrode side remained at 0.43 mm, and no change was observed. On the other hand, before ultrasonic bonding, the total thickness of the lead on the negative electrode side and the thickness of the laminate in the lead area was 0.32 mm; after ultrasonic bonding, the distance from the lower surface of the lead to the highest position of the composite film between the recessed parts of the lead increased to 0.57 mm.
[0457] Then, in the same manner as battery 1-1, the single cell connected with the lead wire is placed inside the outer casing together with the electrolyte, and the outer casing is sealed to obtain battery 1-4. The thickness of the aluminum foil of each positive electrode of battery 1-3 and battery 1-4 is in the range of 11 to 13 μm. The thickness of the polyethylene terephthalate sheet in the composite film of each negative electrode is in the range of 3 to 5 μm, and the thickness of the copper conductive layer is in the range of 0.3 to 1 μm.
[0458] (Evaluation of electrical connection and battery performance)
[0459] For each of batteries 1-1 to 1-4, the connection resistance between the current collector (composite film) and the lead on the positive electrode side or the negative electrode side was examined.
[0460] The connection resistance is measured as follows. First, in the top positive or negative electrode of each battery (i.e., the one farthest from the lead), the active material layer on the upper surface of the composite film as the collector is partially peeled off to expose the conductive layer (aluminum foil or copper foil), and the resistance between the exposed part of the conductive layer and the lead is measured. The distance from the end of the lead side of the collector to the exposed part of the conductive layer is set to about 1 cm. In the measurement of the connection resistance, a battery advanced tester manufactured by HIOKI Corporation is used. Next, the positive or negative electrode is turned over, and the active material layer on the lower surface of the composite film is partially peeled off to expose the conductive layer, and the resistance between the exposed part of the conductive layer and the lead is measured in the same way. Then, the positive or negative electrode that has been measured is peeled off from the counter electrode below it, and the second positive or negative electrode from the top is also measured in the same way. In this way, for all the positive or negative electrodes in each battery (9 positive electrodes in battery 1-1), the connection resistance between the conductive layer on the surface and back of the composite film and the lead is measured in turn to confirm whether electrical connection is achieved. Here, 100 mΩ is used as a reference, and if the measured value of the connection resistance is 100 mΩ or less, it is determined that the electrical connection is achieved.
[0461] As a result, in each of the batteries 1-1 to 1-4, the resistance between the conductive layer (aluminum foil or copper foil) of all the composite films and the lead wire was 100 mΩ or less, confirming that electrical connection was achieved. The connection resistance between the battery 1-1 and the battery 1-3 was compared, and no significant difference was observed. In addition, the connection resistance between the battery 1-2 and the battery 1-4 was compared, and no significant difference was found.
[0462] That is, even when the composite film is used as the current collector instead of the metal foil, the connection resistance is comparable to that when the metal foil is used as the current collector. It can be seen that even when the composite film is used as the current collector instead of the metal foil, the increase in connection resistance can be avoided by forming the connection with the lead wire using ultrasonic bonding.
[0463] Furthermore, the operation of batteries 1-1 to 1-4 was confirmed by charge and discharge tests. It can be seen that by applying the composite film to one or both of the collectors on the positive electrode side and the collectors on the negative electrode side, the effect of reducing the weight of the power storage device can be expected without compromising reliability.
[0464] [Verification of the influence of the shape of the welding head tip on bonding performance 1]
[0465] (Battery 2)
[0466] Next, the single cell of Battery 2 was manufactured in the same manner as Battery 1-1, and the lead wires were connected to the lead regions on the positive and negative sides of the single cell by ultrasonic bonding. However, the shape of the tip of the welding head used for ultrasonic bonding was different from that of the welding head used in manufacturing Battery 1-1.
[0467] Fig.61 : represents the cross-sectional shape of the welding head used in the production of the battery 2. Fig.57 The welding head 80X shown is similarly Fig.61 The welding head 80Y shown in FIG. 1 has a plurality of convex portions 84Y arranged in two directions orthogonal to each other. The center-to-center distance (arrangement pitch) P2 of the convex portions 84Y is equal to Fig.57 The center-to-center distance P1 of the convex portions 84X of the welding head 80X shown in FIG. 1 is the same as 1 mm. The number of convex portions 84Y of the welding head 80Y is also the same as Fig.57 The number of protrusions 84X in the illustrated welding head 80X is the same.
[0468] The shapes of the various parts of the welding head 80Y are as follows. Each convex portion 84Y has a quadrangular pyramid shape with two mutually opposing side surfaces at 90 degrees, and a portion thereof includes a top surface 84a. The width T2 of the top surface 84a in the cross-sectional view when the welding head 80Y is cut along the arrangement direction of the plurality of convex portions 84Y is 0.12 mm, and the width V2 of the bottom of the valley 84v formed between the two convex portions 84Y is 0.05 mm. The distance M2 from the bottom of the valley 84v to the top surface 84a of the convex portion 84Y is 0.415 mm.
[0469] In the production of the battery 2 , the conditions for ultrasonic bonding applied to the connection of the lead on the positive electrode side are as follows.
[0470] Pressing pressure: 0.2MPa
[0471] Amplitude: 100%
[0472] Time of applying vibration: 0.4s
[0473] Vibration direction: lateral vibration (reciprocating motion)
[0474] Oscillation frequency: 40kHz
[0475] Number of engagements: 1
[0476] After obtaining the battery 2, the cross section of the third portion between the lead and the composite film was observed to evaluate the effect of the shape of the tip of the welding head on the bonding properties.
[0477] Fig.62 This is a schematic diagram showing a microscope image of the third portion on the positive electrode side of the battery 2 when observed along the stacking direction of the composite film. As a result of cross-sectional observation of the battery 2, it was found that: similarly to the third portion of the battery 1-1, a concave portion 218 was formed on the upper surface of the lead at a portion compressed in the stacking direction between the convex portion 84Y of the welding head 80Y and the anvil.
[0478] Observe with a microscope Fig.62 The vertical cross section of the composite film shown when it was cut at the position of the LXV-LXV line, as a result, it can be confirmed that a flat area with a width of about 160 μm is formed at the bottom of the recess 218. In addition, it can be seen that: similarly to battery 1-1, in the portion of the upper surface of the lead that overlaps with the recess, most of the resin material is driven out from between the aluminum conductive layers, forming a joint part based on solid phase bonding between the conductive layers in each composite film and solid phase bonding between the conductive layers of two adjacent composite films. In addition, a joint part based on solid phase bonding is also formed between the lead and the conductive layer of the composite film.
[0479] It can be seen that: Figures 57 to 60Compared with the third portion of the battery 1-1 shown in FIG, the depth of the recessed portion is greater in the third portion of the battery 2. This is presumably because the area of the top surface 84a of the protrusion 84Y is reduced in the welding head 80Y compared with the welding head 80X, resulting in that the lead is more strongly compressed.
[0480] In the battery 2, between the recessed portions of the lead wires, the composite film is compressed from left to right by the pressing of the convex portion 84Y of the welding head 80Y against the anvil, and bulges in a direction away from the upper surface of the lead wires. Fig.59 and Fig.60 The difference from the example shown is that, except for a few layers located closer to the lead, no tangled bends are generated in the cross section of the composite film. It is presumed that this is because: Fig.57 The welding head 80X is shown compared to the Fig.61 In the welding head 80Y shown, the distance from the bottom of the valley 84v to the top surface 84a is enlarged. In other words, it is considered that the space between the protrusions 84Y of the welding head 80Y is enlarged, and as a result, more parts of each composite film compressed from the left and right can be accommodated in the valley 84v of the welding head 80Y.
[0481] Thus, it is known that by adjusting the shape of the tip of the welding head used in ultrasonic bonding, the shape of the recessed portion of the lead and the shape of the composite film at the position between the recessed portions of the lead can be controlled within a certain range. In Battery 2, the undulating shape of the lead is shown in a part of the cross section, but it is believed that the undulating shape of the lead itself does not have a significant effect on the characteristics of the single cell when it is used in an electric storage device.
[0482] Will Fig.61 The shape of the protrusion 84Y of the welding head 80Y shown is similar to Fig.57 When the shape of the convex portion 84X of the welding head 80X shown in FIG. 1 is compared, the width of the top surface 84a in the cross-sectional view is larger (T1>T2). That is, the top surface 84a of the convex portion 84X can have a larger area. Therefore, the welding interface between the conductive layer of the composite film and the lead can be expanded, and from the perspective of reducing the connection resistance between the composite film and the lead, Fig.57The shape of the protrusion 84X of the welding head 80X shown is advantageous. However, if the area sandwiched between the protrusion of the welding head and the anvil becomes larger in the insulating layer of the composite film, as a result, a higher pressing pressure tends to be used in order to extrude the resin material of the insulating layer to the outside of the protrusion of the welding head. In addition, in order to expand the space required to accommodate the composite film deformed in a bulging manner due to pressing, it may also be required to expand the arrangement pitch of the protrusion. Therefore, in the case where the protrusion of the welding head used is in the shape of a top surface 84a with a larger area, the area of each third portion of the laminate formed in the lead area can be expanded.
[0483] From the viewpoint of the bonding strength of each bonding portion formed at a position corresponding to the convex portion of the welding head, Fig.61 Compared with the case of the welding head 80Y shown in the figure, the use of Fig.57 The situation of the welding head 80X shown is more favorable. Fig.61 As shown in the welding head 80Y, even if the area of the top surface 84a of each convex portion is relatively small, by increasing the number of convex portions, it is possible to avoid a decrease in the joint strength of the third part as a whole. In the cross-sectional view, the width of the joint portion may be larger than the distance between the centers of two adjacent joint portions, or conversely, it may be narrower than the distance between the centers of two adjacent joint portions. The size relationship between the width of the joint portion and the distance between the centers of two adjacent joint portions may be appropriately changed according to the shape of the welding head.
[0484] (Battery 3)
[0485] Next, a single cell of Battery 3 as a comparative example was manufactured in the same manner as Battery 1-1, and lead wires were connected to the lead regions on the positive and negative electrode sides of the single cell by ultrasonic bonding. However, the shape of the tip of the welding head used for ultrasonic bonding was different from that of the welding head used in manufacturing Battery 1-1 and that of Battery 2.
[0486] Fig.63 : shows the cross-sectional shape of the welding head used in the production of the battery 3. Fig.57 The welding head 80X shown and Fig.61 The welding head 80Y shown is similarly Fig.63The welding head 80Z shown also has a plurality of convex portions 84Z arranged in two directions orthogonal to each other. The center-to-center distance (arrangement pitch) P3 of the convex portions 84Z is 0.4 mm. Each convex portion 84Z has a quadrangular pyramid shape with two mutually opposing side surfaces at 90°, and a portion thereof includes a top surface 84a. The width T3 of the top surface 84a in the cross-sectional view when the welding head 80Z is cut along the arrangement direction of the plurality of convex portions 84Z is 0.06 mm, and the distance M3 from the bottom of the valley 84v formed between the two convex portions 84Z to the top surface 84a of the convex portion 84Z is 0.17 mm.
[0487] In the production of the battery 3 , the conditions for ultrasonic bonding applied to the connection of the lead on the positive electrode side are as follows.
[0488] Pressing pressure: 0.25MPa
[0489] Amplitude: 100%
[0490] Time of applying vibration: 0.4s
[0491] Vibration direction: lateral vibration (reciprocating motion)
[0492] Oscillation frequency: 40kHz
[0493] Number of engagements: 1
[0494] After obtaining the battery 3, the cross section of the third portion between the lead and the composite film was observed to evaluate the effect of the shape of the tip of the welding head on the bonding property.
[0495] Fig.64 It is a schematic diagram showing a microscope image of the third part of the positive electrode side of the battery 3 when observed along the stacking direction of the composite film. As a result of the cross-sectional observation of the battery 3, it can be seen that in the third part of the battery 3, a structure 218z similar to a concave portion is formed in the portion compressed between the convex portion 84Z of the welding head 80Z and the anvil on the upper surface of the lead, but it is deformed in a shape that is not a part of the lead undulating, but the whole lead undulating.
[0496] Observe with a microscope Fig.64 The vertical cross section of the composite film cut at the position of the LXIX-LXIX line can be confirmed that the concave portion of the upper surface of the lead includes a flat area with a width of about 140 μm at the bottom. In battery 3, although a structure 218z similar to a concave portion is formed on the upper surface of the lead, the connection between the conductive layer of the composite film and the lead is not sufficiently formed, and the lead as a whole is deformed.
[0497] Thus, it is considered that one reason for the unexpected excessive deformation on the lead wire is that a higher pressure is required to remove the resin material from between the conductive layers of each composite film due to the narrow intervals between the convex parts at the front end of the welding head or the small height of the convex parts. In addition, it is speculated that when the intervals between the convex parts at the front end of the welding head are narrow or the height of the convex parts is small, the valley portion formed at the front end of the welding head is small, so the size of the space for accommodating each composite film compressed from the left and right becomes insufficient.
[0498] [Verification of the influence of the shape of the welding head tip on the bonding performance 2]
[0499] (Electrode structure 4-1)
[0500] The shape of the front end of the welding head was changed to further evaluate the bonding property between the lead and the composite film. The number of composite films as the collector on the positive electrode side was set to 10, and the laminated body of the composite film was connected to the lead by ultrasonic bonding, thereby producing electrode structure 4-1. Except for changing the shape of the front end of the welding head used in ultrasonic bonding, the laminated body of the composite film and the lead were connected in the same manner as battery 1-1.
[0501] In the ultrasonic bonding of the lead wires in the electrode structure 4-1, Fig.57 The welding head 80X shown in the figure similarly uses a welding head having a plurality of convex parts in the shape of a quadrangular pyramid arranged in two directions orthogonal to each other. The arrangement pitch of the convex parts is 0.62 mm, and the width of the top surface of the convex part in the cross-sectional view when the welding head is cut along the arrangement direction of the convex parts is 0.21 mm.
[0502] Before ultrasonic bonding, the total thickness of the lead on the positive electrode side and the thickness of the laminate in the lead area was 0.16 mm. In contrast, after ultrasonic bonding, the distance from the lower surface of the lead to the highest position of the composite film between the recessed portions of the lead increased to 0.29 mm.
[0503] (Electrode structure 4-2)
[0504] The shape of the front end of the welding head was changed to further evaluate the bonding property between the lead wire and the composite film. Electrode structure 4-2 was produced in the same manner as electrode structure 4-1, except that the shape of the welding head used in ultrasonic bonding was changed. In ultrasonic bonding of electrode structure 4-2, a welding head with a convex arrangement pitch of 0.3 mm and a top surface width of each convex portion of 0.1 mm was used.
[0505] Before ultrasonic bonding, the total thickness of the lead on the positive electrode side and the thickness of the laminate in the lead area was 0.16 mm. In contrast, after ultrasonic bonding, the distance from the lower surface of the lead to the highest position of the composite film between the recessed portions of the lead increased to 0.2 mm.
[0506] For electrode structure 4-1 and electrode structure 4-2, the connection resistance between the collector and the lead on the positive electrode side was measured by the same method as battery 1-1 to battery 1-4. For electrode structure 4-1, a connection resistance value roughly equivalent to the case where metal foil is used for the collector was obtained. However, in electrode structure 4-2, a sufficiently low value could not be obtained as the value of the connection resistance. According to the comparison between electrode structure 4-1 and electrode structure 4-2, when the configuration pitch of the protrusions is an inappropriate value (for example, the configuration pitch of the protrusions of the welding head is too small relative to the number of composite films in the single cell, etc.), it may not be possible to properly form an electrical connection between the electrode and the lead in the single cell.
[0507] [Verification of the influence of the number of composite films on bonding properties]
[0508] Next, electrode structures 5-1 to 5-4 were produced by changing the number of composite films connected to the lead wires in the same process as electrode structure 4-1. Furthermore, the extent to which the composite film laminate protruded from the lead wires between the recesses formed in the lead wires was compared.
[0509] (Electrode structure 5-1)
[0510] In the electrode structure 5-1, the number of positive electrodes was set to 5. The thickness of the laminate in the lead region before ultrasonic bonding was 0.04 mm. After ultrasonic bonding, the distance from the upper surface of the lead to the highest position of the composite film between the recessed portions of the lead increased to 0.07 mm. That is, the distance from the upper surface of the lead to the highest position of the composite film between the recessed portions of the lead increased by 75% compared to before ultrasonic bonding.
[0511] (Electrode structure 5-2)
[0512] In the electrode structure 5-2, the number of positive electrodes was set to 10. The thickness of the laminate in the lead region before ultrasonic bonding was 0.07 mm. After ultrasonic bonding, the distance from the upper surface of the lead to the highest position of the composite film between the recessed portions of the lead increased to 0.17 mm. That is, the distance from the upper surface of the lead to the highest position of the composite film between the recessed portions of the lead increased by 143% compared to before ultrasonic bonding.
[0513] (Electrode structure 5-3)
[0514] In the cell of the electrode structure 5-3, the number of positive electrodes was set to 15. In the electrode structure 5-3, similarly to the cell 1-2, a lead wire having a thickness of 0.2 mm was bonded to the stack of 15 composite films.
[0515] The thickness of the laminate in the lead region before ultrasonic bonding was 0.11 mm. After ultrasonic bonding, the distance from the upper surface of the lead to the highest position of the composite film between the recesses of the lead increased to 0.31 mm. That is, the distance from the upper surface of the lead to the highest position of the composite film between the recesses of the lead increased by 182% compared to before ultrasonic bonding.
[0516] (Electrode structure 5-4)
[0517] In the electrode structure 5-4, the number of positive electrodes was set to 20. Similarly to the electrode structure 5-3, in the electrode structure 5-4 as well, a lead wire having a thickness of 0.2 mm was bonded to the laminated body of the composite film.
[0518] The thickness of the laminate in the lead region before ultrasonic bonding was 0.15 mm. After ultrasonic bonding, the distance from the upper surface of the lead to the highest position of the composite film between the recesses of the lead increased to 0.48 mm. That is, the distance from the upper surface of the lead to the highest position of the composite film between the recesses of the lead increased by 220% compared to before ultrasonic bonding.
[0519] In this way, the change in the distance from the upper surface of the lead to the highest position of the composite film before and after the ultrasonic bonding process will vary depending on the number of composite films connected to the lead by ultrasonic bonding. However, even when the number of composite films is set to be the same, the change can also vary depending on the shape of the front end of the welding head used in ultrasonic bonding. The degree of protrusion of the composite film between the recesses of the lead can be different in size depending on the arrangement pitch of the protrusions of the welding head, the area of the area on the surface of the protrusions of the welding head that contacts one of the uppermost layers contained in the laminate of the composite film, etc.
[0520] [Industrial Applicability]
[0521] The electrode for the power storage device of the embodiment of the present invention is useful for power supplies of various electronic devices, motors, etc. The power storage device of the embodiment of the present invention can be applied to, for example, power supplies for vehicles represented by bicycles and passenger cars, power supplies for communication devices represented by smartphones, power supplies for various sensors, and power supplies for unmanned eXtended Vehicles (UxV).
[0522] [Explanation of Reference Numerals]
[0523] 11, 21: First conductive layer (of composite film)
[0524] 12, 22: Second conductive layer (of composite film)
[0525] 14, 24: Layer 1
[0526] 24r: Resin
[0527] 25: Joint
[0528] 28a: Opening (of the concave portion of the composite film)
[0529] 28p: convex part
[0530] 51, 61, 61P to 61V: Concave portion (on the upper surface of the lead)
[0531] 61a: Opening (of the recessed portion on the upper surface of the lead)
[0532] 62, 62A, 62B: Concave portion (on the lower surface of the lead)
[0533] 63: Concave part (of composite film)
[0534] 80, 80A, 80B, 80X~80Z: horn
[0535] 84, 84A, 84B, 84X~84Z: (the convex part of the welding head)
[0536] 90: Anvil
[0537] 94: (the) convex part of anvil
[0538] 100A~100D: Lithium-ion secondary battery
[0539] 100E: Electric double layer capacitor
[0540] 200A~200E: Single battery
[0541] 210A~210E: 1st electrode (positive electrode)
[0542] 210t: Leading area
[0543] 212, 212E: First material layer (active material layer)
[0544] 215, 215A~215D: Composite membrane
[0545] 220A~220E: Second electrode (negative electrode)
[0546] 220t: Leading area
[0547] 222, 222E: Second material layer (active material layer)
[0548] 225, 225A~225D: Composite membrane
[0549] 228, 228U, 228V: Concave part (of composite film)
[0550] 240J: Part 3
[0551] 250, 260: Conductor plate (lead)
[0552] 270, 270A, 270B: Layer 3 (diaphragm)
[0553] 270Ca, 270Cb, 270E: Layer 3 (Separator)
[0554] 290, 290E: Electrolytes
[0555] 300: Exterior body.
Claims
1. A secondary battery, characterized in that: including an outer casing and an electrode for a power storage device, The electrode for the power storage device comprises: a conductive plate having a portion located inside the outer casing and a portion located outside the outer casing, and having a first surface including at least one first recessed portion, and a second surface located on the opposite side of the first surface, the first surface having a first region located outside the first recessed portion; and a first composite film disposed in the internal space of the outer casing, comprising a first layer containing an insulating material, a first conductive layer, and a second conductive layer, wherein the first layer is located between the first conductive layer and the second conductive layer; The first conductive layer of the first composite film is connected to the conductor plate in the first recessed portion. The second conductive layer of the first composite film is connected to the first conductive layer at a position overlapping with the first recessed portion when viewed from a normal direction of the first region of the conductor plate.
2. The secondary battery according to claim 1, wherein: The portion overlapping the first recess when viewed from the normal direction includes an organic substance located deeper than the first region in the first surface.
3. The secondary battery according to claim 1 or 2, characterized in that: The first conductive layer of the first composite film has a third surface facing the first region of the conductor plate, and the second conductive layer of the first composite film has a fourth surface located on the side opposite to the third surface with respect to the first layer. The distance along the normal direction from a portion of the fourth surface of the second conductive layer that overlaps with the first recessed portion of the conductive plate when viewed in the normal direction to the conductive plate is smaller than the distance along the normal direction from a portion of the fourth surface of the second conductive layer that overlaps with the first region of the conductive plate when viewed in the normal direction to the conductive plate.
4. The secondary battery according to any one of claims 1 to 3, characterized in that: The bottom of the first recess includes a flat region.
5. The secondary battery according to any one of claims 1 to 4, characterized in that: It also includes: a second composite film having a third conductive layer, a fourth conductive layer, and a second layer containing an insulating material, The second layer is located between the third conductive layer and the fourth conductive layer, At least a portion of the third conductive layer is located between the fourth conductive layer and the first composite film. The fourth conductive layer has a fifth surface located on the opposite side to the third conductive layer. The third conductive layer is connected to the first conductive layer and the second conductive layer of the first composite film at a position overlapping with the first recessed portion when viewed from the normal direction. The fourth conductive layer is connected to the third conductive layer at a position overlapping with the first recess when viewed from the normal direction. The fifth surface of the fourth conductive layer includes, in a portion overlapping the first recess when viewed from the normal direction, a portion closer to the second surface than a portion of the first surface of the conductor plate located in the first region.
6. The secondary battery according to any one of claims 1 to 5, characterized in that: The second surface of the conductor plate has one or more second recessed portions.
7. The secondary battery according to claim 6, wherein: The one or more second recessed portions include a second recessed portion arranged at a position overlapping with the first recessed portion when viewed from the normal direction.
8. The secondary battery according to claim 6 or 7, characterized in that: The at least one first concave portion includes: two first concave portions arranged along a first direction perpendicular to the normal direction, The one or more second recessed portions include a second recessed portion located between the two first recessed portions when viewed from the normal direction.
9. The secondary battery according to any one of claims 1 to 7, characterized in that: The at least one first recessed portion includes two first recessed portions arranged along a first direction perpendicular to the normal direction.
10. The secondary battery according to claim 8 or 9, characterized in that: The first layer of the first composite film has a portion whose thickness increases as it moves from one of the two first recesses to the other.
11. The secondary battery according to any one of claims 8 to 10, characterized in that: The first conductive layer has a first arc-shaped portion that is curved in a cross section perpendicular to the first region. The first arc-shaped portion is located between the two first recessed portions.
12. The secondary battery according to any one of claims 8 to 11, characterized in that: A portion of the sixth surface of the first conductive layer located on the opposite side of the conductive plate is bent in a direction away from the conductive plate in a cross section perpendicular to the first region. The portion of the sixth surface is located between the two first recessed portions.
13. The secondary battery according to any one of claims 8 to 12, characterized in that: The first conductive layer of the first composite film has first folded portions that overlap each other when viewed in the normal direction by being bent and folded. The first folded portion is located between the two first recessed portions.
14. The secondary battery according to any one of claims 11 to 13, characterized in that: The second conductive layer has a second arc-shaped portion that is curved in a cross section perpendicular to the first region. The second arc-shaped portion is located between the two first recessed portions.
15. The secondary battery according to any one of claims 11 to 14, characterized in that: A portion of the surface of the second conductive layer on the side away from the conductive plate is bent in a direction away from the conductive plate in a cross section perpendicular to the first region. The portion of the surface of the second conductive layer is located between the two first recessed portions.
16. The secondary battery according to any one of claims 11 to 15, characterized in that: The second conductive layer of the first composite film has second folded portions that overlap each other when viewed in the normal direction by being bent and folded. The second folded portion is located between the two first recessed portions.
17. The secondary battery according to any one of claims 8 to 16, characterized in that: The two first recesses respectively have openings located on the first surface of the conductor plate. A maximum value of a width of one of the openings is greater than a minimum value of a distance from the one of the openings to the other of the openings.
18. The secondary battery according to any one of claims 8 to 16, characterized in that: The two first recesses respectively have openings located on the first surface of the conductor plate. A maximum value of a width of one of the openings is smaller than a minimum value of a distance from the one of the openings to the other of the openings.
19. The secondary battery according to any one of claims 8 to 16, characterized in that: The two first recesses respectively have openings located on the first surface of the conductor plate. A width of one of the openings along the first direction is smaller than a width of the one of the openings along the normal direction and a second direction perpendicular to the first direction.
20. The secondary battery according to any one of claims 8 to 16, characterized in that: The two first recesses respectively have openings located on the first surface of the conductor plate. One of the openings includes a portion whose width changes along the first direction or a second direction perpendicular to the first direction.
21. The secondary battery according to any one of claims 8 to 16, characterized in that: The two first recesses respectively have openings located on the first surface of the conductor plate. One of the openings has a curved shape.
22. The secondary battery according to any one of claims 8 to 16, characterized in that: The two first recesses respectively have openings located on the first surface of the conductor plate. One of the openings has a serpentine shape.
23. The secondary battery according to any one of claims 17 to 20, characterized in that: The opening has a rectangular shape.
24. The secondary battery according to any one of claims 1 to 7, characterized in that: The at least one first recessed portion includes a plurality of first recessed portions arranged along a third direction and a fourth direction that are perpendicular to and different from the normal direction.
25. The secondary battery according to claim 24, characterized in that: The plurality of first recesses are at least three first recesses arranged along the third direction, and each of the plurality of first recesses includes at least three first recesses having an opening located on the first surface of the conductor plate. The at least three first recesses respectively include: a first group and a second group of two first recesses sandwiching the first region and adjacent to each other along the third direction; A distance between openings of two first recessed portions included in the first group is different from a distance between openings of two first recessed portions included in the second group.
26. The secondary battery according to any one of claims 1 to 25, characterized in that: The first composite film has third recessed portions recessed toward the conductor plate, the third recessed portions being located at positions on the opposite side of the conductor plate and corresponding to the first recessed portions of the conductor plate.
27. The secondary battery according to claim 9, characterized in that: The power storage device electrode further includes: a first active material layer disposed on a portion of the first composite film; The first layer of the first composite film comprises: a first portion located between the two first recesses; and a second portion overlapping the first active material layer, A thickness of at least a portion of the first portion along the normal direction is greater than a thickness of the second portion.
28. The secondary battery according to claim 27, characterized in that Also includes: The second electrode; a second active material layer located on the second electrode; and An electrolyte and a separator are located between the first active material layer and the second active material layer.
29. The secondary battery according to any one of claims 1 to 26, wherein include: a second electrode; and An electrolyte is located between a portion of the first composite membrane and the second electrode.
30. The secondary battery according to claim 29, wherein: Also includes: a first active material layer disposed on the portion of the first composite film; a separator disposed between the first active material layer and the second electrode; and a second active material layer located on the second electrode, The second active material layer is located between the second electrode and the separator.
31. The secondary battery according to claim 28 or 30, characterized in that: At least one of the first active material layer and the second active material layer contains a material capable of absorbing and releasing lithium ions.
32. The secondary battery according to claim 31, characterized in that: The first conductive layer contains aluminum.
33. The secondary battery according to claim 31, characterized in that: The first conductive layer contains copper.
34. The secondary battery according to any one of claims 31 to 33, characterized in that: One of the first active material layer and the second active material layer contains carbon.
Citation Information
Patent Citations
Nonaqueous secondary battery
JP2012155974A
Active material for electric double layer capacitor, electrode for electric double layer capacitor, and electric double layer capacitor
JP2020064971A
Battery connections and metallized film components in energy storage devices having internal fuses
US20200373584A1
Laminated battery
JP2009038004A